Species and geographical origin discrimination of cinnamon using UV-Vis spectroscopy combined with chemometrics - Xiao-Dong Sun; Zhu Pan; Yan-Yan Tang; Qi Zuo; Min Zhang; Huan Liang; Peng-Jiao Wang; Xiu-Li Gao (Food Control, 2027)

Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

Genetic analysis and reporting from whole-exome sequencing data in 1052 patients with intellectual disability - Xin Pan; Guanhua Qian; Li Liu; Xu Zhang; Yang Yang; Qingyun Zhang; Xianglan Tang; Nanyan Yang; Lijie Dong; Hong Yao; Xiaojing Dong; Bo Tan (Journal of Molecular Medicine, 2026)

3D chromatin architecture-related genes orchestrate LUAD evolution and therapy resistance: insights from integrative machine learning and spatial single-cell mapping - Yahao Jing; Yuying Xing; Yangyang Liu; Ningxuan Zhang; Yudan Pan; Wenhao Zhang; Chenglin Zhu; Zhenyue Zhong; Guoyu Zhang; Ji-Cheng Li; Xiaotao Dong (Functional & Integrative Genomics, 2026)

Decoding epigenetic drived heterosis in upland cotton (Gossypium hirsutum L.) through Multi-omics integration - Na Dong; Xiaoli Geng; Shoupu He; Zhen Peng; Hongge Li; Yuqing Li; Daowu Hu; Qinghua Yang; Xiaoping Pan; Xiongming Du; Qinglian Wang (Functional & Integrative Genomics, 2026)

Regional contrasts in phytoplankton communities and organic carbon pools: Hydrographic forcing and zooplankton grazing in the Cosmonaut and Cooperation Seas - Cuiting Li; Dong Li; Jun Zhao; Ji Hu; Xinliang Wang; Guijun Guo; Jianming Pan; Bin Wu; Peisong Yu; Weiping Sun; Guanbei Wu; Haifeng Zhang; et al. (Marine Pollution Bulletin, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Updated fiber models for post-earthquake residual displacement estimation of reinforced concrete piers - Wei Liu; Mingke Li; Shaowei Wu; Zhongguo Guan; Xin Jiang; Pan Dong (Soil Dynamics and Earthquake Engineering, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Combining knowledge-based training data generation and deep learning algorithms for mapping surface water bodies, wetlands, and paddy rice in Northeast Asia - Chenchen Zhang; Xiangming Xiao; Cheng Meng; Xinxin Wang; Leikun Yin; Dehua Mao; Shenglai Yin; Yuan Yao; Li Pan; Baihong Pan; Xuebin Yang; Yuanwei Qin; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Surface reconstruction-induced multi-strategy approach enables enhanced structural integrity and long-term cycling stability of Li-rich Mn-based cathode - Yin Zhao; Dongye Liu; Linyao Dong; Liaona She; Xu Xue; Zhijun Wu; Shengnan He; Chao Zheng; Jiantuo Gan; Chenchen Li; Mingchang Zhang; Yaxiong Yang; et al. (Chemical Engineering Journal, 2026)

The gut-liver axis mediates the hepatoprotective effect of mulberry polysaccharide MBPS-02A - Yuqing Sun; Shi Zhong; Jinxi Huo; Qin Xiao; Huanyan Ma; Xintian Dong; Jiayi Feng; Meiliang Pan; Zhengshun Wen; Yougui Li (Carbohydrate Polymers, 2026)

Asymmetric alternating current-assisted adsorption for polycarboxylic acid scale inhibitor removal and ion interference mitigation - Shuoxun Dong; Haixia Pan; Changyu Wang; Siyu Chen; Li Chen (Journal of Environmental Chemical Engineering, 2026)

Rapid aerobic sludge granulation in a dual-zone sedimentation tanks continuous-flow reactor using CaCl2/FeCl3-conditioned surplus sludge - Shuangxia Wu; Dong Xu; Zengrui Pan; Zhaoxian Li; Ailan Yan; Shuyun Wu; Jun Li; Chaoguang Gu (Journal of Environmental Chemical Engineering, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

The dual role of Ni: From promotion to suppression of hydrodesulfurization in NiMoW catalysts - Fengyu Tian; Guangzheng Sun; Xianfu Zeng; Jingjing Liu; Yuhao Liang; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; Bin Liu; Chenguang Liu; et al. (Chemical Engineering Journal, 2026)

Direct interspecies electron transfer-based simplified microbial consortia for high-efficiency conversion of lignocellulose to methane: Construction, metabolic pathway and performance optimization - Chunlei Dong; Jiayu Pan; Yuan Li; Meng Liu; Yang Li; Zhiqiang Zhao; Yaobin Zhang (Bioresource Technology, 2026)

DIMBOA and melatonin mediate a recruitment feedback loop between wheat and Bacillus pseudomycoides to alleviate herbicide stress - Chunran Zhou; Canping Pan; Tao Zhang; Peijuan Miao; Xiaoying Wan; Dong Li (Journal of Hazardous Materials, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

The characteristics and mechanism of phosphorus adsorption and release of extracellular polymeric substances in biofilms based on phosphorus recovery - Min Ni; Zhiwen Dong; Ruijing Wu; Yu Wang; Wenle Yang; Can Zhang; Dapeng Li; Yong Huang; Lu Li; Yanyan Ding; Chuanming Yang; Yang Pan (Bioresource Technology, 2026)

Efficient de novo biosynthesis of salidroside in Yarrowia lipolytica via integrated metabolic and glycosyltransferase engineering - Wen-Yan Tang; Xi-Yu Duan; Hu-Hu Liu; Chong Wang; Yue-Dong He; Hu Pan; Chang-Zhu Li; Xiang-Yang Lu; Xiao-Jun Ji; Yun Tian; Xiao-Na Yang (Bioresource Technology, 2026)

Experimental and theoretical research on the impact resistance performance of thin-walled viscoelastic vibration isolation devices - Juncheng Yao; Zhao-Dong Xu; Xing-Huai Huang; Jingbo Song; Fengfeng Ran; Xiaoning Mo; Jianchun Li; Zhongwen Pan (Soil Dynamics and Earthquake Engineering, 2026)

Retraction notice to “Response of C:N:P stoichiometry to long-term drainage of peatlands: Evidence from plant, soil, and enzyme” [Sci. Total Environ. 919 (2024) 170688] - Shengzhong Wang; Yaoyao Du; Shasha Liu; Junxiao Pan; Fan Wu; Yingzhuo Wang; Yuting Wang; Hongkai Li; Yanmin Dong; Zucheng Wang; Ziping Liu; Guodong Wang; et al. (Science of The Total Environment, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Spatial distribution of per- and polyfluoroalkyl substances in the Yellow River basin: Role of suspended sediment on the PFAS partition and accumulation - Yanan Li; Yawen Li; Yitao Pan; Wenjing Lv; Fengfeng Dong; Qiusheng He; Lijuan Huo; Yang Cui; Ke Zhang; Jiayin Dai; Jianhui Tang (Journal of Hazardous Materials, 2026)

Mechanistic insights into KOH-regulated biochar derived from waste Myriophyllum aquaticum biomass for 1O2-mediated degradation of 2,4,6-trichlorophenol - Guangya Zhou; Dong Zhang; Zhengzheng Lou; Miaomiao Zhao; Dihua Wu; Suling Zhang; Ying Pan; Ting Lü; Hongting Zhao; Jun Lin; Li Lu; Ming Zhang (Journal of Environmental Management, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Effects of cold atmospheric plasma treatment on the structure and functional properties of Tenebrio molitor larvae protein - Yaxi Zhou; Dong Xu; Hualei Chen; Fei Pan; Xiangxin Li; Wenli Tian (Innovative Food Science & Emerging Technologies, 2026)

Isolation and characterization of polar lipid-rich milk fat globule membrane ingredients from buttermilk and butter serum - Yin Pei; Kuolin Si; Mengna Yu; Yue Pan; Xiao-Dong Li; Xuexing Zong; Lu Liu; Xiuxiu Zhang; Shuaiyi Ma; Qingquan Yan (International Dairy Journal, 2026)

Synergistic inhibition and microbial adaptation in anammox systems under long-term salinity and fulvic acid stress - Wenjun Yin; Yilin Li; Aodong Pan; Junwei Wu; Xiaomei Su; Xiao Xiao; Feng Dong; Liang Xu; Chongjun Chen; Hailu Fu; Faqian Sun (Bioresource Technology, 2026)

Seasonal pollution characteristics, sources and environmental impact of volatile organic compounds in urban area in central China - Lihua Pan; Dong Zhang; Bowen Zhang; Minghao Yuan; Yifei Xu; Jie Tao; Ruiqin Zhang; Xiao Li (Atmospheric Pollution Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Long-term creep failure behaviour and a thermodynamics-based predictive model for high-molecular-weight polyethylene (HMPE) fiber yarns used in ocean engineering - Zhang He; Zeng Ji; Jin Bowen; Gao Pan; Chiate Chou; Dong Hailei; Li Hangyu (Ocean Engineering, 2026)

Uncovering a hidden hazard in pesticide risk assessment: Metal ion-catalyzed pre-analytical artifacts of feproxydim in paddy matrices - Meijing Ji; Jiayue Li; Wei Wang; Jing Wang; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Journal of Hazardous Materials, 2026)

Synergistic pore-acidity engineering in hierarchical H-beta zeolites for molecular sieving of ethylcyclohexane - Xue Ma; Xianjie Wang; Jinhui He; Jingdong Gou; Yaning Zhao; Akang Liu; Shuo Feng; Louwei Cui; Huiyong Chen; Jun Yang; Liuyi Pan; Dong Li (Fuel, 2026)

Morphology-driven catalytic performance of H-ZSM-5 in benzene alkylation with syngas - Qicheng Li; Xihu Zhao; Xiaobo Song; Juan Dong; Zhitong Zhao; Pan Hao; Qi Shi; Xuekuan Li (Fuel, 2026)

Potential of supramolecular solvent-based extraction for decontamination of volatile organic compounds in mechanically recycled polyethylene terephthalate - Jinxin Liang; Tianlong Zhang; Can Xu; Jingjing Pan; Huai-Ning Zhong; Qizhi Su; Anqi Cui; Hanke Li; Dan Li; Ben Dong (Food Packaging and Shelf Life, 2026)

Synergistic NaCl-modulated refinement and in-situ SnO2 embedding for ultrasensitive isobutanol sensing in SnO2-Fe2O3 heterojunctions - Kaiwei Wang; Jianing Qian; Chi Ma; Lei An; Yingzhu Li; Likun Pan; Tianjun Ni; Dong Liu (Chemical Engineering Journal, 2026)

Sustainable poly(ester-amide) with superior intrinsic barrier performance recycled from poly(ethylene terephthalate) waste - Maolin Li; Ying Zheng; Chang Zeng; Haoran Chen; Xueyan Yun; Tungalag Dong; Dong Xu; Yu Bai; Xiaoyan Deng; Pengju Pan (Chemical Engineering Journal, 2026)

Strontium and cesium accumulation in soil-rice system: Influencing factors and predictive modeling - Hong-Ling Chen; Bao-Min Yao; Zi-Yang Pan; Dong-Li Sun; Guang Yang; Tian-Ran Sun; Guo-Xin Sun (Soil Ecology Letters, 2026)

Transcriptional profiling reveals brain region-specific changes in gene expression induced by chronic unpredictable mild stress between stress-susceptible and stress-resilient mice - Xiaoyu Chen; Yi Cao; Xianlong Zhao; Yang Li; Zhenhua Song; Juntao Wang; Dong Pan (Psychopharmacology, 2026)

Pacific oyster (Crassostrea gigas) stocking density as a regulator of nitrous oxide emissions: connecting sediment biogeochemistry and microbial functional genes - Shengjie Xu; Li Li; Xuan Dong; Miaojun Pan; Wenwen Jiang; Xiangli Tian; Yunwei Dong; Shuanglin Dong; Ramón Filgueira (Marine Life Science & Technology, 2026)

Enhancement of self-heating decarbonization and activation of coal gangue by pellet sintering process - Wenzhuo Ma; Tao Dong; Deqing Zhu; Jian Pan; Zhengqi Guo; Congcong Yang; Siwei Li; Wuju Zhang; Yuping Yang; Denan Hou (Process Safety and Environmental Protection, 2026)

Dissecting the genetic architecture of silique-related traits in rapeseed (Brassica napus L.) through genome-wide association studies and transcriptome analysis - Cuiping Zhang; Guangze Li; Ruolin Gong; Yunfei Zhang; Pan Lu; Chunyan Dai; Niannian Fan; Wu Yao; Xue Shi; Jungang Dong; Jihong Hu (Theoretical and Applied Genetics, 2026)

Exploring the connection of marine heatwaves and mesoscale eddies in the South China Sea - Wenjin Sun; Yindi Wang; Mingshen Xie; Yongyan Pan; Chunhui Li; Jinlin Ji; Yang Yu; Kenny Thiam Choy Lim Kam Sian; Changming Dong (Journal of Oceanology and Limnology, 2026)

Carbon availability and redox potential regulate carbon mineralization in peat soils under contrasting moisture regimes - Guangyuan Xu; Jiye Cai; Yuting Wang; Yang Wang; Junxiao Pan; Zucheng Wang; Hongkai Li; Yanmin Dong; Shasha Liu; Ziping Liu; Zhiwei Xu; Shengzhong Wang (Applied Soil Ecology, 2026)

Differential tissue-specific thermotolerance and cellular recovery mechanisms in Haliotis discus hannai under thermal stress - Dong Huang; Xinxin Li; Mingzhu Pan; Yue Liu; Gaochan Qin; Zhichu Chen; Xiaojun Yu; Kangsen Mai; Wenbing Zhang (Aquaculture International, 2026)

Supranutritional dietary vitamin D3 promoted the skin wound healing in turbot, Scophthalmus maximus L. - Zhichu Chen; Yuanyuan Fang; Yuanting Li; Xinhua Chen; Mingzhu Pan; María Ángeles Esteban; Kangsen Mai; Yanjiao Zhang; Dong Huang (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

The response of East China Sea internal tides to ocean warming: intensified while maintaining seasonal contrasts - Bingtian Li; Haidong Pan; Dong Jiang; Shujiang Li (Ocean Modelling, 2026)

Enhancing hydrogen production from anaerobic sludge fermentation via sodium dichloroisocyanurate pretreatment: Performance and mechanisms - Jiamin Zhang; Haiyang Zhang; Zhiren Cao; Wei Zhang; Qiqi Dong; Dongyi Li; Min Pan; Yingqun Ma; Qiuxiang Xu; Jonathan W.C. Wong (Journal of Environmental Chemical Engineering, 2026)

Why Does Braising Enhance the Aroma Profile of Xinjiang Braised–Roasted Chicken? Insights into Precursor Conversion and Aroma Formation Pathways - Ke Bi; Yue Liu; Dong Han; Xinwei Li; Yinfeng Lei; Hong Pan; Ping Yang; Chunhui Zhang; Marie-laure Fauconnier (Food Research International, 2026)

Low-carbon renovation of old residential blocks: An envelope-focused assessment framework for carbon reduction effects and economic benefits - Shen Xu; Yichen Dong; Hongxin Guo; Zhen Yu; Bo Pan; Congyue Qi; Gaomei Li (Energy and Buildings, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Curcumin protects against difenoconazole-induced kidney injury in carp by inhibiting ferroptosis through the Nrf2/GPX4 axis - Shasha Zhang; Xinran Li; Yaxin Gao; Qian Dong; Xiaomin Jin; Pan Shi; Jingquan Dong (Fish Physiology and Biochemistry, 2026)

Angelicin attenuates sepsis-associated splenic injury by targeting NF-κB/JAK2/STAT3 and PI3K/Akt pathways to inhibit inflammation and apoptosis - Enzhuang Pan; Huilin Sun; Zhihao Ma; Shasha Zhang; Yedan Liu; Zihan Xu; Yusa Li; Xiaomin Jin; Heng Wang; Jingquan Dong (Toxicology and Applied Pharmacology, 2026)

Spatiotemporal variability of PAHs and PAEs in sediments driven by hydrological rhythms in Danjiangkou Reservoir, China: Multisource analysis to machine-learning prediction - Li Lin; Lei Dong; Haibo Zhang; Guochuan Yin; Zhuqi Chen; Haiyang Jin; Xingrui Qi; Xiong Pan; Yu Gao (Process Safety and Environmental Protection, 2026)

Hydrochar improves the dewaterability of digestate from anaerobic co-digestion of food waste and waste activated sludge: A neglected benefit - Qiuxiang Xu; Haiyang Zhang; Qiqi Dong; Dongyi Li; Jialin Liang; Min Pan; Jiamin Zhang; Jonathan W.C. Wong (Journal of Environmental Management, 2026)

Gelatin-based film applying cyclodextrin metal-organic frameworks for controlled release of thyme essential oil: Development, characterization and application in fruit preservation - Yaqi Li; Yibo Song; Guoxin Dong; Demei Meng; Mingfei Pan; Shuo Wang (Food Hydrocolloids, 2026)

UV-induced aging creates adsorption hotspots: Oxygen-containing functional groups on nanoplastics dictate the adsorption behavior of ciprofloxacin - Fengfeng Ma; Yilei Dong; Zhiyi Xue; Jian Zhang; Hao Zhao; Jiayun Lu; Jiayi Fu; Yan Pan; Xiaoyun Li (Environmental Research, 2026)

Solar-driven catalytic platforms for closed-loop carbon cycling: CO2 assisting biomass conversion - Jingwen Jiang; Yiheng Wang; Yuanjie Li; Junxi Huang; Weiping Zhang; Dan Wang; Dong Xu; Dong Fu; Pan Zhang; Lemeng Wang; Kun Zhao (Bioresource Technology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A multi-pronged approach to understanding the antifungal mechanism of chitooligosaccharide against Fusarium oxysporum, a major pathogen causing potato dry rot - Airong Huang; Jie Ren; Jiaomei Zhang; Yuxin Jia; Xiaoxiao Zhou; Peidong Liu; Chunlin Zhang; Xiaoqing Huang; Xunguang Luo; Lei Shi; Liting Yang; Yujia Zhao; et al. (Postharvest Biology and Technology, 2026)

Material source and genesis analysis of lithium-rich claystone in Balun Mahai Salt Lake, Qaidam Basin - Fan Zhang; Xiwei Qin; Yuliang Ma; Sha Yang; Tong Pan; Jianzhou Chen; Chenglin Liu; Chengwang Ding; Ziwen Jiang; Dong Zhang; Qingkuan Li; Genhou Wang; et al. (Journal of Geochemical Exploration, 2026)

Sustainable recovery of spent ternary cathode materials via integrated sulfation roasting and oxalate co-precipitation - Liumei Teng; Xinbao Pan; Jiangqi Liu; Dong Wang; Kehong Li; Xu Duan; Xinlin Yu; Jinping Shuai; Yourui Tian; Boliang Liu; Weizao Liu (Journal of Environmental Chemical Engineering, 2026)

Acid-induced structural reorganization of fish myofibrillar protein gels: trade-off between elasticity and stability - Linli Fang; Ruoyi Hao; Xinlin Liu; Xianbing Xu; Shengjie Li; Xuanpeng Wang; Dan Wang; Yugang Wang; Hairong Sun; Xiuping Dong; Jinfeng Pan (Food Research International, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

Response mechanisms of abalone Haliotis discus hannai to lead (Pb) exposure in vitro: insights into autophagy, endoplasmic reticulum stress and apoptosis - Yue Liu; Dong Huang; Mingzhu Pan; Xinxin Li; Gaochan Qin; Xiaojun Yu; Ze Zhang; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2026)

Study on the effect and mechanism of Fenton-like reaction based on UV/H2O2 to degrade sulfamethoxazole in water - Baochang Zhou; Guifang Li; Zhangbin Pan; Bin Dong; Zhenqi Du; Baiqiang Zhang; Mei Li; Yonglei Wang; Ruibao Jia (Environmental Science and Pollution Research, 2026)

Lysosomal protein SLC38A9 regulates arginine-mediated autophagy, ER stress, and apoptosis in abalone Haliotis discus hannai - Yue Liu; Dong Huang; Xinxin Li; Mingzhu Pan; Gaochan Qin; Xiaojun Yu; Mengxi Yang; Yaan-Kit Ng; Kangsen Mai; Wenbing Zhang (Marine Life Science & Technology, 2026)

Adaptability and stress response mechanisms of abalone Haliotis discus hannai to cadmium in vitro and in vivo - Yue Liu; Dong Huang; Mingzhu Pan; Xinxin Li; Gaochan Qin; Xiaojun Yu; Zhenhua Wu; Ze Zhang; Kangsen Mai; Wenbing Zhang (Aquaculture, 2026)

Variability in N2O emissions at the sediment–water interface in coastal aquaculture: The role of stocking densities and feeding strategies - Shengjie Xu; Miaojun Pan; Wenwen Jiang; Xuan Dong; Xiangli Tian; Yunwei Dong; Li Li (Marine Pollution Bulletin, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Enhanced CO2 desorption from monoethanolamine solution using TiO(OH)2-modified diatomite catalyst - Pan Zhang; Zhongfa Zha; Jiawen Yang; Xinbo Wang; Jianwen Song; Shuming Du; Liwen Li; Kun Zhao; Dong Fu; Lemeng Wang; Jun Ke; Pengfei Qu (Process Safety and Environmental Protection, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Dynamic response of a monopile offshore wind turbine under aero-hydrodynamic interaction - Zhiyuan Wu; Kai Gao; Changbo Jiang; Wei Pan; Bin Li; Chunlei Li; Zhichao Dong; Bin Deng; Jie Chen (Ocean Engineering, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Okadaic acid induces oxidative stress and immunotoxicity in zebrafish: involvement of the p53 pathway and behavioral alterations - Duo Chen; Siming Pan; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Functionalized UiO-66-NO2 for selective separation of coal-derived C8 cyclohexane isomers: A dual mechanism of geometric confinement and electronic recognition - Xianjie Wang; Yaning Zhao; Hengsheng Wei; Yi Wang; Jingdong Gou; Jinhui He; Xue Ma; Louwei Cui; Liuyi Pan; Jiaojiao Liu; Dong Li (Chemical Engineering Journal, 2026)

Study on CO2 capture performance and regeneration enhancement of ionic liquid/deep eutectic solvent composite absorbents - Shihui Wang; Futang Liu; Xiaole Dong; Dongmei Lv; Guodong Zhang; Xiaokun Li; Jinkai Pan; Qingmei Meng; Xinpeng Liu (Chemical Engineering Journal, 2026)

Techno-economic analysis of offshore green methanol production in South China Sea - Dong Lin; Liyu Zhang; Chenxi Pan; Haitao Hu; Jia Yang; Bo Tong; Zhiyu Li; Xin Zhang (Chemical Engineering Journal, 2026)

Oxygen vacancy enriched alumina supported Ni nanocatalysts for highly selective acetylene hydrogenation - Hedan Yao; Yuanjun Che; Dong Huang; Yi Qin; Yuchen Niu; Wenhong Li; Liuyi Pan; Dong Li (Chemical Engineering Journal, 2026)

Research and Application of the Unsteady Heat Transfer Analytical Model for SAGD - Guoqing Feng; Pan Wang; Xiangjin Liang; Junhui Zou; Aiping Zheng; Ning Li; Dong Song; Yang Liu; Wenzhi Song; Huan Liu; Haiyang Yu (Transport in Porous Media, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Spatiotemporal variation of bacterial β-diversity under ecological water replenishment in a Yellow River Delta coastal river: Contributions and assembly mechanisms of rare and abundant subcommunities - Xing Liu; Dandan Ding; Yanfang Xu; Xiaoqiu Yu; Hao Dong; Yun Li; Guanpin Yang; Baohua Zhu; Yan Zhao; Kehou Pan (Marine Pollution Bulletin, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Nanoselenium-driven reduction in chemical fungicide usage: Eco-safety enhancement in pepper Phytophthora capsici control - Zhijia Zhang; Tianbing Zhou; Canping Pan; Mengmeng Li; Jialing Wang; Xiaoyi Wang; Shuai Wang; Zhan Hu; Ranfeng Sun; Dong Li (Pesticide Biochemistry and Physiology, 2025)

A novel spatio-temporal dataset for vessel traffic flow prediction - Yuanlong Chen; Mingyang Pan; Zongying Liu; Dong Zhang; Shaoxi Li; Yang Wei; Yang Zhang (Ocean Engineering, 2025)

Aluminum-modified diatomite efficiently catalyzes the CO2 desorption to achieve low-energy consumption regeneration of amine solution - Pan Li; Xin He; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Wenyang Lu; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

Soil pH and bacterial diversity synergistically regulate trace element transfer and accumulation in soil-rice systems - Ying Ding; Bao-Min Yao; Hong-Ling Chen; Dong-Li Sun; Zi-Yang Pan; Qing Zeng; Chang-Chun Zhai; Yuan-Kun Liu; Guo-Xin Sun (Soil Ecology Letters, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Cross-modal 2D-3D feature matching: simultaneous local feature description and detection across images and point clouds - Wei Ma; Yucheng Huang; Shengjun Tang; Xianwei Zheng; Zhen Dong; Liang Ge; Jianping Pan; Qingquan Li; Bing Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Analysis of structural failure in fast-spinning small bodies - Qian Pan; Xiangyu Li; Dong Qiao (Icarus, 2025)

Drainage reorganization near the eastern margin of the Tibetan Plateau as a result of fluvial response to differential uplift enhanced by isostatic compensation - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Zijuan Dong; Xiaohua Li; Meiling Zhong; Renzhe Pan; Ningyi Li; Rob Westaway (Global and Planetary Change, 2025)

Shear performance of damaged concrete T-beams strengthened with diagonal NSM Fe-SMA bars - Yu Sun; Jiahang Li; Hong Zhu; Zhiqiang Dong; Yijie Pan; Ligang Zhao; Elyas Ghafoori (Engineering Structures, 2025)

Creation of new rice germplasm with cross-resistance to auxin herbicides picloram and dicamba by genome editing of OsAFB4 - Haonan Wei; Dongling Li; Kexin Xie; Siying Lou; Guojun Dong; Fu Guo; Guiwei Lian; Xiangjian Pan; Zhanghui Zeng; Ning Han; Zhenyu Gao; Hongwu Bian (Theoretical and Applied Genetics, 2025)

Antioxidant capacity and root K+ retention: regulation mechanisms of drought tolerance in sweetpotato - Chengkang Xue; Minfei Sheng; Jiayuan Zhu; Jinping He; Zhiyuan Pan; Zhaoxia Liao; Jian Sun; Yaoyao Wu; Yang Dong; Zongyun Li; Jingran Liu (Plant Cell Reports, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

An Introduction to the Synthesis Community Integrated Model Version 2 (SYCIM2.0) and Its Simulation of the East Asian Summer Monsoon - Wenjun Liang; Wenjie Dong; Danya Xu; Bin Wang; Li Liu; Yanli Tang; Jie Yang; Song Wang; Fuhai Dao; Duofan Zheng; Chenhao Li; Fei Liu; et al. (Advances in Atmospheric Sciences, 2025)

On the hotspot-Sun angular offset in urban thermal anisotropy - Wenfeng Zhan; Lu Jiang; Guanwen Chen; Jian Hang; Pan Dong; Shasha Wang; Long Li; Huilin Du (Remote Sensing of Environment, 2025)

Thermal damage evolution of carbon fiber/epoxy composites for hydrogen storage tanks under fire conditions - Pan-Deng Liu; Bei Li; Xin Ma; Bing Han; Guang-Yin Li; Dong-Lei Sun; Chen Song (Process Safety and Environmental Protection, 2025)

Trophodynamic mechanisms of per- and polyfluoroalkyl substances in oligotrophic ecosystem from the Tibetan Plateau river - Yanan Li; Jiao Ren; Yawen Li; Fengfeng Dong; Qiusheng He; Yang Cui; Ke Zhang; Zhentao Wang; Xinqi Xin; Yitao Pan; Jianhui Tang (Journal of Hazardous Materials, 2025)

In-depth investigation of the spatial variations of DOM components in sediments under the influence of cascade dams and their interactions with microbial communities - Fangjie Zhang; Longfei Wang; Xiong Pan; Lei Dong; Weijie Wu; Yi Li; Li Lin (Journal of Environmental Management, 2025)

Comprehensive review on pretreatment and recovery technology of spent hydrogenation catalysts: Current developments and bottlenecks - Deqing Zhu; Tao Dong; Jian Pan; Wenzhuo Ma; Zhengqi Guo; Siwei Li (Journal of Environmental Chemical Engineering, 2025)

Characterization of OSA-starch/tea polyphenol complexes with enhanced oil-water interfacial properties by molecular dynamics simulation and isothermal titration calorimetry - Lidan Pan; Xiaorui Liu; Die Dong; Li Guo; Meng Zhao; Bo Cui (Food Chemistry, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Enhanced CO2 capture efficiency via catalytic Fe2O3-modified multi-walled carbon nanotubes in monoethanolamine - Lingling Li; Xin He; Pan Li; Xiaoqin Li; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Maohong Fan; Yuan Zhou (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Dynamic Spatio-Temporal Modeling for Vessel Traffic Flow Prediction with FSTformer - Dong Zhang; Haichao Xu; Yongfeng Guo; Shaoxi Li; Yinyin Lu; Mingyang Pan (Journal of Marine Science and Engineering, 2025)
With the rapid growth of global shipping, accurate vessel traffic prediction is essential for waterway management and navigation safety. This study proposes the Fusion Spatio-Temporal Transformer (FSTformer) to address non-Gaussianity, non-stationarity, and spatiotemporal heterogeneity in traffic flow prediction. FSTformer incorporates a Weibull–Gaussian Transformation for distribution normalization, a hybrid Transformer encoder with Heterogeneous Mixture-of-Experts (HMoE) to model complex dependencies, and a Kernel MSE loss function to enhance robustness. Experiments on AIS data from the Fujiangsha waters of the Yangtze River show that FSTformer consistently outperforms baseline models across multiple horizons. Compared with the best baseline (STEAformer), it reduces MAE, RMSE, and MAPE by 3.9%, 1.8%, and 6.3%, respectively. These results demonstrate that FSTformer significantly improves prediction accuracy and stability, offering reliable technical support for intelligent shipping and traffic scheduling in complex waterways.

Microbial transformation of geniposide in Gardeniae Fructus under the fermentation with Aspergillus niger DQWM-G11 - Xiao-Xin Xu; Xue-Jiao Li; Ke-Wen Pan; Liang Deng; Shu-Biao Xia; Jian-Wei Dong (Natural Product Research, 2025)

Spatial heterogeneity and seasonal succession of phytoplankton community in the Cosmonaut Sea, East Antarctica: driving forces and implications - Guanbei Wu; Dong Li; Jun Zhao; Jianming Pan; Ji Hu; Peisong Yu; Weiping Sun; Haifeng Zhang; Changfeng Zhu; Cuiting Li (Frontiers in Marine Science, 2025)
Understanding the dynamics of the phytoplankton community in the marginal seas of the Southern Ocean is crucial for delineating its role in global carbon cycling. This study investigated spatiotemporal variations in phytoplankton community structure and organic carbon pools in the Cosmonaut Sea, East Antarctica, with an emphasis on spatial heterogeneity and environmental drivers during late austral summer (February). Water samples were collected from 15 stations during the 40th Chinese Antarctic Research Expedition (CHINARE-40, February 2024), and nutrient, pigment, particulate organic carbon (POC), and dissolved organic carbon (DOC) concentrations were quantified. The CHEMTAX analysis revealed that the phytoplankton community was dominated by diatoms (38% ± 16%), dinoflagellates (22% ± 12%), and Prymnesiophyceae Phaeocystis antarctica (12% ± 10%). Diatoms and P. antarctica contributed significantly to POC (r = 0.36, p < 0.01) and DOC (r = 0.69, p < 0.01), respectively. Spatial distribution patterns displayed pronounced heterogeneity; large ice-edge diatoms dominated cold, high-light, and shallow mixed-layer regions, while small pelagic diatoms and dinoflagellates dominated in stratified, nutrient-limited, and low-light environments. Comparative analysis with adjacent Southern Ocean sectors further highlighted how distinct water masses shape niche competition. Furthermore, our results suggest a trend toward phytoplankton miniaturization, with increasing prevalence of dinoflagellates and P. antarctica under projected positive phases of the Southern Annular Mode, potentially diminishing biological carbon pump efficiency and weakening carbon sequestration. Collectively, these findings clarify how the Cosmonaut Sea phytoplankton community responds to environmental variability, providing essential insights into biogeochemical cycling and carbon budget dynamics in the Southern Ocean under climate change.

In vitro culture and comparative pathogenic characteristics of two ciliates prevalent in the sea cucumber Apostichopus japonicus - Dongmei Yue; Peipei Li; Jingwei Jiang; Ying Dong; Bai Wang; Shan Gao; Gang Song; Hongjuan Sun; Feifei Zhang; Pingzhe Jiang; Yongjia Pan; Zunchun Zhou (Aquaculture, 2025)

Prediction of next-day 1-km canopy urban heat island by integrating a multi-block convolutional neural network with satellite- and ground-based observations - Shuang Ge; Wenfeng Zhan; Jiufeng Li; Long Li; Pan Dong; Xiang Li; Chenguang Wang; Chunli Wang; Yihan Gao (Sustainable Cities and Society, 2025)

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Synergistic mechanism for preparation of high-performance ceramsite from coal gangue and iron ore tailings - Wenzhuo Ma; Wuju Zhang; Jian Pan; Deqing Zhu; Tao Dong; Zhengqi Guo; Congcong Yang; Siwei Li (Process Safety and Environmental Protection, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Ni/Al₂O₃ structures on defective carbon coating derived from pyrolysis of nitrogen-enriched coal tar pitch for acetylene hydrogenation - Hedan Yao; Nannan Zhao; Dong Huang; Yi Qin; Yuchen Niu; Wenhong Li; Liuyi Pan; Dong Li (Chemical Engineering Journal, 2025)

Ni-Mo alloy anchored on carbon nitride coated γ-Al2O3 for hydrodeoxygenation of lignin-derived phenols into aviation fuel-range cycloalkanes - Zifan Wu; Lu Chen; Yacong Deng; Fengyu Tian; Guangzheng Sun; Yuting Qiu; Yichuan Li; Yuan Pan; Bin Liu; Bin Dong; Yongming Chai (Chemical Engineering Journal, 2025)

Microbial pterins as potential indicators of organic carbon dynamics in estuarine and coastal sediments - Kang Mei; Yitong Pan; Danny Alejandro Osorio; Lizhe Cai; Hualong Hong; Mohammad Mazbah Uddin; Song Wang; Xin Xiao; Xuri Dong; Li Chen; Shicong Xiao; Deli Wang (CATENA, 2025)

Production of avermectins by Streptomyces avermitilis through solid-state fermentation using agro-industrial waste - Guozhong Du; Zhuoxu Dong; Zhengduo Wang; Minghui Pan; Yanyan Zhang; Wensheng Xiang; Shanshan Li (Bioresource Technology, 2025)

JsSAMDC promotes polyamine synthesis and flowering genes to synergistically regulate female flower bud differentiation - Jinyan Chen; Wenwen Li; Chunxiang Li; Yuanqi Huang; Jian Peng; Dong Huang; Mengmeng Liu; Xuejun Pan; Wen’ e Zhang (Plant Cell Reports, 2025)

Regulation of LCN-2/PI3K/Akt on TNF-α induced inflammatory response of porcine intramuscular adipocytes - Xiaoying Dong; Xiaona Zeng; Yongjian Li; Yiming Yan; Shuang Gao; Yanfei Chen; Shengqiu Tang; Meiqi Liang; Yiyi Pan; Xiaonan Zhou; Wei Luo; Yuchen Tang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Homologues of PFOA substitutes in a semi-closed bay near source region: contamination status and risk assessments - Dawei Shi; Yitao Pan; Wenke Dou; Fengfeng Dong; Jian Zhang; Xinqi Xin; Yanan Li; Jiayin Dai; Jianhui Tang (Marine Pollution Bulletin, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

Climate change alters the radial growth responses of P. schrenkiana and J. jarkendensis to climate extremes in the Eastern Pamirs - Tiane Yang; Yonghui Wang; Tongwen Zhang; Dong Pan; Kexiang Liu; Huaming Shang; Abula Arman; Li Qin; Ruibo Zhang (Dendrochronologia, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Deep reinforcement learning based performance optimization of hybrid system for base-isolated structure and shape memory alloy-inerter - Chunxiang Li; Jie Zhao; Hang Pan; Liyuan Cao; Qingsong Guan; Zhao-Dong Xu (Engineering Structures, 2025)

Energy efficiency and comfort: analysis of thermal responses and behaviors of residents with high and low air conditioning dependency - Haiyan Yan; Yu Pan; Mengru Dong; Hui Zhang; Jiang Li; Shengkai Zhao (Energy and Buildings, 2025)

Engineering the Ni-N3 microenvironment: Electronic and spatial effect significantly improves the performance of the thermal catalytic acetylene semi-hydrogenation - ZiHao Tao; Hedan Yao; Guoqing Qi; Hengrui Li; Yi Qin; Louwei Cui; Liuyi Pan; Dong Li; Wenhong Li (Chemical Engineering Journal, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Highly reactive iron in Ross Sea surface sediments: Spatial heterogeneity, environmental controls and implications for Antarctic shelf deposition - Wenhao Huang; Jun Zhao; Xiaoze Guo; Dong Li; Ji Hu; Haifeng Zhang; Changfeng Zhu; Jianming Pan; Jianfang Chen (Science China Earth Sciences, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Impact of residential morphology on outdoor thermal comfort and building energy consumption in winter and summer: A case study - Minghao Wang; Yichen Dong; Wei Liao; Bo Pan; Sensheng Li; Junchao Duan; Shen Xu (Urban Climate, 2025)

Distinct vertical profiles of microbial communities and functional genes between different lake sediment layers mediated by nutrients in the sediments and pore waters - Yu Gao; Bo Zhu; Li Lin; Quanxi Xu; Wei Zhang; Xiong Pan; Lei Dong (Science of The Total Environment, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Bacillus subtilis JATP-3 Improves Nitrogen Metabolism by Regulating Intestinal Flora and AKG in Weaned Piglets - Feng He; Xueying Jin; Kecheng Sun; Lei Zhao; Wenyan Yang; Xuefeng Zhang; Xiaoqing Dong; Yuan Zhao; Li Pan; Nan Bao; Hui Sun (Probiotics and Antimicrobial Proteins, 2025)

miR- 34c- 5p targets ROCK1 expression to inhibit kidney injury in diabetic nephropathy rats through MAPK/ERK signaling pathway - HuaJuan Wei; Ye Li; HongDe Liu; Li Pan; HuiLing Duo; ShaoYing Dong (In Vitro Cellular & Developmental Biology - Animal, 2025)

Dose-dependent inflammatory and neurotoxic effects of polypropylene microplastics in Nile tilapia evidenced by internal extractive electrospray ionization high-resolution mass spectrometry metabolomics - Xiaokang Wu; Susu Pan; Ming Li; Jiaxin Dong; Yining Wang; Chenni Huang; Tao Qiu; Yu Gu; Dapeng Liang (Environmental Chemistry Letters, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Unveiling the mechanism and driving factors of pharmaceutical and personal care product (PPCP) removal in wastewater treatment plants - Shaoyang Li; Zhen Gao; Tianyi Chen; Zhile Pan; Dianbao Li; Yanran Dong; Junjie Li; Yanli Zhang; Sihan Cui; Weiling Sun; Nan Xu (Journal of Environmental Management, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Partitioning behavior of short-chain legacy and novel perfluorinated substances (PFAS) between dissolved and particulate phases in a river-estuary-coast continuum - Dawei Shi; Yitao Pan; Yi Luo; Fengfeng Dong; Jian Zhang; Xinqi Xin; Yanan Li; Jiayin Dai; Jianhui Tang (Environmental Pollution, 2025)

A bee-inspired multisensory spiking neuron with Humid-Visual fused perception for authenticity recognition - Keyuan Pan; Chen Chen; Xiujuan Li; Duoyi Zhu; Kang Chen; Kaili Wang; Xinkai Qian; Xuemei Dong; Min Xu; Hongchao Sun; Zifan Li; Fei Xiu; et al. (Chemical Engineering Journal, 2025)

High-entropy engineered Bi0.47Na0.47Ba0.06TiO3-based weakly coupled relaxor ferroelectrics with quasi-linear polarization for enhanced energy storage performance - Yue Pan; Yu Zhang; Qinpeng Dong; Jiangping Huang; Shize Zhao; Xiuli Chen; Xu Li; Huanfu Zhou (Chemical Engineering Journal, 2025)

Thermosensitive poly (NVCL-co-GelMA) nanogels as a delivery platform for rectal administration of 5-ASA in ulcerative colitis - Rongjiao Sun; Limei Zhu; Xianzhu You; Rong Chen; Jiante Li; Rongrong Pan; Yueqi Jin; Hua Zhou; Ying Tan; Jiajia Dong; Wanle Hu (Chemical Engineering Journal, 2025)

Pore microstructure and mass transfer dynamics in thick electrodes for high energy density lithium-ion batteries - Bowei Li; Shanfeng Wang; Pan He; Zhenyao Huang; Bo Mai; Xia Zhang; Yuhang Chen; Yuehua Wen; Xiaqing Ran; Chunhua Han; Ingo Manke; Kang Dong; et al. (Chemical Engineering Journal, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Analysis of slab buckling rockburst of surrounding rock under dynamic and static combined disturbance - Feng Chen; Ruxuan Li; Kaixing Wang; Yanhong Du; Chun’an Tang; Yishan Pan; Zhuo Dong (Tunnelling and Underground Space Technology, 2025)

Phanerochaete chrysosporium hyphae bio-crack, endocytose and metabolize plastic films - Lele Li; Zhi Guo; Xingpan Guo; Dazhuang Dong; Ting Fan; Lin Yao; Yuanyuan Zha; Jianyu Kong; Yaodan Dai; Tao Pan (Journal of Hazardous Materials, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Dynamic performance of TEPA-impregnated carbon nanofibers composites for direct air carbon capture in fixed bed columns - Si Chen; Xin He; Pan Li; Lingling Li; Meng Wang; Yulin Li; Qi Xu; Yanxia Sun; Chunxi Hai; Shengde Dong; Luxiang Ma; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

A novel approach to bulk-phase hydrogenation using an extremely high-loading sulfide NiMoW/SiO2 catalyst - Fengyu Tian; Guangzheng Sun; Xianfu Zeng; Shuwen Xie; Yidi Wang; Zifan Wu; Bin Liu; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; et al. (Fuel, 2025)

Low-cost diatomite-loaded ZrO(OH)2 as an efficient green catalyst for amine-based carbon capture - Pan Li; Xingdong Qiu; Lingling Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Xin He; Yuan Zhou (Fuel, 2025)

Efficient carbon dioxide capture and reduced desorption energy consumption with bifunctional aluminium-modified MWCNTs catalyst - Lingling Li; Xin He; Pan Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2025)

Preparation and characterization of covalent starch-protein-tea polyphenol complexes with enhanced interfacial properties - Die Dong; Tenglong Geng; Lidan Pan; Xiaorui Liu; Chenxi Yu; Chao Yuan; Li Guo; Meng Zhao; Bo Cui (Food Research International, 2025)

Rapid dewatering and discharge of residual water quality through geotextile filtration coupled with flocculant treatment of contaminated dredged mud - Tao Wang; Chunrong Wang; Dingwei Liu; Danping Yang; Pan Li; Bin Dong (Environmental Research, 2025)

Realizing ultrahigh energy storage performance in bismuth sodium titanate-based ceramics via quasi-linear polarization response design - Jiangping Huang; Yue Pan; Qingpeng Dong; Yu Zhang; Xiuli Chen; Xu Li; Huanfu Zhou (Chemical Engineering Journal, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Monthly variations in nutrient utilization along 45°E transect in the Cosmonaut Sea, East Antarctica during austral summer - Xufeng Yang; Dong Li; Jun Zhao; Cai Zhang; Changfeng Zhu; Shunan Cao; Guangfu Luo; Gaojing Fan; Yongming Sun; Ji Hu; Haifeng Zhang; Peisong Yu; et al. (Acta Oceanologica Sinica, 2025)

Sources and distribution characteristics of chromophoric dissolved organic matter in the Cosmonaut Sea and the Cooperation Sea, Antarctica - Ji Hu; Siyou Xue; Bin Zhou; Jun Zhao; Dong Li; Gaojing Fan; Disong Yang; Leilei Zhang; Haifeng Zhang; Peisong Yu; Cai Zhang; Xufeng Yang; et al. (Acta Oceanologica Sinica, 2025)

Spatial dynamics of phytoplankton assemblages and organic carbon stock in the highly productive Amundsen Sea Polynya and adjacent seasonal ice zone - Dong Li; Jun Zhao; Ji Hu; Jianming Pan; Jianfeng He; Yongming Sun; Peisong Yu; Xufeng Yang; Cai Zhang; Haifeng Zhang; Weiping Sun; Gaojing Fan (Acta Oceanologica Sinica, 2025)

Influence of austral summer sea ice melting timing on particle fluxes and composition in Prydz Bay, East Antarctica - Changfeng Zhu; Yufei Ding; Wenhao Huang; Jun Zhao; Dong Li; Haifeng Zhang; Yanhong Xu; Cai Zhang; Ji Hu; Shunan Cao; Guangfu Luo; Yongming Sun; et al. (Acta Oceanologica Sinica, 2025)

Best Practices and Recommendations for Non-Liquid Matrices Bioanalysis - Faye Vazvaei-Smith; Wenkui Li; Omar S. Barnaby; Sanjeev Bhardwaj; Juyao Dong; Carolyne Dumont; Carmen Fernández-Metzler; Brian Geist; Mohamed Hassanein; Amanda Hays; Anna Ilinskaya; Eugene P. Kadar; et al. (The AAPS Journal, 2025)
The analysis of Non-Liquid Matrices (NLMs) can provide key information on many aspects in drug discovery and development. These include but are not limited to drug uptake and distribution, engagement and modulation, and target exposure. A thorough understanding of these aspects is fundamental to the progression of drug development. In many cases, such an understanding can only be achieved through quantitative analysis of NLMs. Such dependence can lead to bottlenecks in the drug development process—as the practices and regulations that govern bioanalysis of conventional liquid matrices typically cannot be directly applied to NLMs. This paper strives to fill this crucial gap. To this end, subject matter experts from across the industry, through the auspices of the AAPS Bioanalytical Community, have combined their collective best practices for NLM bioanalysis in this paper. Certainly, this endeavor came with challenges, the most prominent of which also serves as the impetus for this project, the lack of literature on NLM bioanalysis dealing with different types of NLM, analysis rigor, and best practices to draw from. This paper aims to serve as a comprehensive set of best practices drawn from the experiences of leading scientists across the industry—for NLM bioanalysis in drug development. Graphical Abstract

Effects of water temperature and its interaction with dietary lipid levels on growth performance and immunity of Pacific abalone Haliotis discus hannai - Mingzhu Pan; Yanlin Guo; Dong Huang; Shuoli Ma; Xinxin Li; Mengxi Yang; Wanyou Zhou; Kangsen Mai; Wenbing Zhang (Aquaculture, 2025)

Enhanced iodinated disinfection byproducts formation in iodide/iodate-containing water undergoing UV-chloramine sequential disinfection: Machine learning-aided identification of reaction mechanisms - Zhen-Ning Luo; Huan He; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Meng-Yuan Xu; Heng-Xuan Zhao; Zheng-Xiong Zheng; Ren-Jie Pan; Chen-Yan Hu; Chao Zeng; Mohamed Gamal El-Din; et al. (Water Research, 2025)

China's non-energy-intensive sectors have greater carbon reduction potential: Based on a three-tier SDA approach from energy substitution perspective - Chang Qin; Feng Dong; Yangfan Li; Xiaoyun Zhang; Yuling Pan; Caixia Li; Jue Cui (Environmental Impact Assessment Review, 2025)

Micro-mechanism of basal stresses in steady rock-ice mixture flows: Insights from 2D DEM simulations - Quan Zhang; Li-jun Su; Zhi-bo Dong; Yong-liang Pan (Cold Regions Science and Technology, 2025)

Total flavonoids from Rosa rugosa Thunb.: A comprehensive review of its extraction and purification process, chemical composition, biological effect and applications - Guangfeng Dong; Lina Lv; Gang Ding; Fengying Li; Pan Zhao; Jiangting Liu; Hongyan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Additive release and prediction of biofilm-colonized microplastics in three typical freshwater ecosystems - Tao Pan; Zhi Guo; Shuheng Hu; Dazhuang Dong; Jie Li; Xue Yang; Yaodan Dai; Lele Li; Feiyan Wu; Zhangzhen Wu; Shanshan Xi (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Sedimentary dynamic processes affected by tropical cyclones and anthropogenic forcing in a small-scale estuary: The Sheyang River Estuary, China - Gang Yang; Chunhui Li; Xiang Fan; Jin Wang; Xishan Pan; Xue Han; Xiangzhen Meng; Chengyi Zhao; Changming Dong (Marine Geology, 2025)

Characteristics, sources, and concentration prediction of endocrine disruptors in a large reservoir driven by hydrological rhythms: A case study of the Danjiangkou Reservoir - Lei Dong; Xingrui Qi; Li Lin; Kefeng Zhao; Guochuan Yin; Liangyuan Zhao; Xiong Pan; Zhiguang Wu; Yu Gao (Journal of Hazardous Materials, 2025)

Macroscale structures of layered double hydroxides: A review of formation strategies and applications in water treatment - Yubo Pan; Linrui Li; Dong Liu; Fenghe Wang; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2025)

Investigation into enhanced performance of toluene and Hg0 stimulative abatement over Cr-Mn oxides co-modified columnar activated coke - Jiajie Wang; Jie Liu; Lei Gao; Dong Xie; Caiting Li; Liping Xiang; Huiyu Xiong; Jiaqi Xie; Tianren Zhang; Yueguo Pan (Journal of Environmental Sciences, 2025)

Sensitive and portable intelligent detection platform construction and dietary risk assessment of procymidone in Chinese leek, cowpea and celery - Binbin Zhang; Shi Li; Wentao Zhang; Youpu Cheng; Zhenjiang Liu; Ning Zhang; Jun Xu; Xiaohu Wu; Fengshou Dong; Yongquan Zheng; Xinglu Pan (Food Chemistry, 2025)

Interactions between Dendrobium officinale polysaccharide and κ-carrageenan: Rheological and functional properties - Rongxiang Guo; Yihang Sun; Minjie He; Zhuochen Yao; Dong Peng; Yanli Li; Yafei Wang; Pan Li; Bing Du (Food Hydrocolloids, 2025)

The emerging roles of particulate matter-changed non-coding RNAs in the pathogenesis of Alzheimer's disease: A comprehensive in silico analysis and review - Hui-Xian Zeng; Shuang-Jian Qin; John Andersson; Shen-Pan Li; Qing-Guo Zeng; Jia-Hui Li; Qi-Zhen Wu; Wen-Jie Meng; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Guang-Hui Dong; et al. (Environmental Pollution, 2025)

Fabrication of a Single-Atom Mo catalyst for significantly enhanced hydrodesulfurization activity of dibenzothiophene - Bin Liu; Hongyang Lv; Fengyu Tian; Wenkui Xue; Xingxing Cui; Yuan Pan; Yichuan Li; Bin Dong; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2025)

N-doped biochar supported Ni-Co alloy catalyst for efficient hydrocracking of enzymatic hydrolysis lignin to monophenols in water - Zifan Wu; Yacong Deng; Fengyu Tian; Yidi Wang; Na Fan; Guangzheng Sun; Yichuan Li; Yuan Pan; Bin Liu; Bin Dong; Han Hu; Yongming Chai (Chemical Engineering Journal, 2025)

Design and numerical analysis of an offshore methanol synthesis process through CO2 hydrogenation - Dong Lin; Liyu Zhang; Chenxi Pan; Jia Yang; Haitao Hu; Bo Tong; Zhiyu Li; Xin Zhang (Chemical Engineering Journal, 2025)

Agroforestry increases soil carbon sequestration, especially in arid areas: A global meta-analysis - Jiachen Pan; Shuotong Chen; Dejun He; Hao Zhou; Ke Ning; Ning Ma; Kaiyi Li; Dongxi Liao; Wenhai Mi; Qicong Wu; Congzhi Zhang; Zhi Dong (CATENA, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Efficient secretory expression, purification, and characterization of lipase in Pseudomonas aeruginosa M18, with multifunctional applications in diagnostics - Yunbo Liu; Pan Zhu; Lingyuan Kong; Jing Wang; Chengdong Ji; Yuanli Li; Lichun Dong; Weijing Yi (World Journal of Microbiology and Biotechnology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

OCTN2 expression and function in the Sertoli cells of testes from patients with non-obstructive azoospermia - Dong Li; Nan Jiang; Minjia Pan; Linzi Ma; Yunchong Huang; Xiaoheng Xu; Xinyan Yang; Yongtong Zhu; Hua Shi; Shan-Chao Zhao (Journal of Molecular Histology, 2025)

Fasting time after feeding affects the evaluation of metabolic response in abalone Haliotis discus hannai to nutrients using dietary methionine as an example - Yue Liu; Hao Chen; Wenhao Fan; Dong Huang; Xinxin Li; Mingzhu Pan; Gaochan Qin; Xiaojun Yu; Kangsen Mai; Wenbing Zhang (Aquaculture, 2025)

Influence of offshore cage culture on surface sediment in the Yellow Sea Cold Water Mass: Assessed with stable isotope and fatty acid analyses - Miaojun Pan; Shuai Shi; Li Li; Xiangli Tian; Qinfeng Gao; Shuanglin Dong; Chengyue Liu (Science of The Total Environment, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Research advances in citrus polyphenols: green extraction technologies, gut homeostasis regulation, and nano-targeted delivery system application - Yahui Liu; Ning Yan; Qin Chen; Lezhen Dong; Ying Li; Peifang Weng; Zufang Wu; Daodong Pan; Lingyi Liu; Mohamed A. Farag; Lei Wang; Lianliang Liu (Critical Reviews in Food Science and Nutrition, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Increased soil bacteria-fungus interactions promote soil nutrient availability, plant growth, and coexistence - Dong Hu; Xuehui Zhou; Gaoyuan Ma; Jiahao Pan; Huan Ma; Yongfu Chai; Yunshi Li; Ming Yue (Science of The Total Environment, 2024)

First insight into the formation of transformation products of a biopesticide guvermectin in rat and its health risk - Yuan Shi; Xinglu Pan; Xiaohu Wu; Jun Xu; Wensheng Xiang; Zhiyuan Li; Yongquan Zheng; Xiangjing Wang; Fengshou Dong (Science of The Total Environment, 2024)

Improving zinc reduction and removal from pellets of zinc-bearing dusts via vacuum microwave-assisted carbothermal reduction process - Wuju Zhang; Tao Dong; Deqing Zhu; Yin Jiang; Jian Pan; Zhengqi Guo; Siwei Li; Wenzhuo Ma (Process Safety and Environmental Protection, 2024)

AhGSNOR1 negatively regulates Al-induced programmed cell death by regulating intracellular NO and redox levels - Chunliu Pan; Xia Li; Changge Jian; Yunyi Zhou; Aiqin Wang; Dong Xiao; Jie Zhan; Longfei He (Plant Science, 2024)

Novel Venturi injector reactor design and application in ammonia nitrogen wastewater treatment - Weiwen Wang; Litong Zhou; Chaojie Li; Guiyong Li; Yekui Chen; Qingpeng Pan; Zhixin Yu; Yangshuo Dong; Jihai Duan (Journal of Water Process Engineering, 2024)

Understanding the potential of coal gangue as photocatalyst for antibiotic degradation: The role of abundant oxygen vacancies and electron-hole pairs - Jihong Dong; Jiabang Li; Shuyue Zheng; Quan Chen; Min Wu; Peng Yi; Yu Huang; Bo Pan (Journal of Water Process Engineering, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

Ameliorative effects of Trichosanthes kirilowii Maxim. seed oil on hyperlipidemia rats associated with the regulation of gut microbiology and metabolomics - Weili Chen; Zhangbao Zhou; Ruida Qi; Jun Zhou; Huiying Liang; Pinxi Huang; Zebin Zou; Ling Dong; Hua Li; Bing Du; Pan Li (Food Research International, 2024)

Effect of low-salinity seawater transient on antioxidant capacity, muscle quality and intestinal microorganism of crucian carp (Carassius auratus gibelio) - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2024)

Glucose-induced glycation enhances the foaming properties of Trichosanthes kirilowii seed protein isolate: Insights into structure, interfacial behavior, and proteomics - Dong Peng; Weijuan Huang; Hanxiao Bao; Wanyue Ding; Xiangmin Pan; Guosen Li; Ling Dong; Weiwen Li; Jianping Chen; Pan Li; Bing Du (Food Hydrocolloids, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Asymmetric coordinative modulation boosting the activity and thermal stability of Pt1/CeO2 for CO oxidation under harsh condition - Lijun Ni; Yuwei Zhou; Wei Tan; Hong Li; Dong Wang; Qi Zhang; Bing Yang; Jing Xu; Ying Zhang; Chengsi Pan; Yongfa Zhu; Fudong Liu; et al. (Chemical Engineering Journal, 2024)

A transformer-based forecasting model for F 10.7 index and its application study on the Chinese Langfang dataset - Hongwei Ye; Yanfang Zheng; Xuebao Li; Liang Dong; Wengeng Huang; Jing Wang; Shuainan Yan; Hengrui Lou; Pengchao Yan; Shunhuang Zhang; Xuefeng Li; Yi Ling; et al. (Advances in Space Research, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Organic carbon cycling in the sediments of Prydz Bay, Eastern Antarctica: Implications for a high carbon sequestration potential - Peisong Yu; Dong Li; Jun Zhao; Jianming Pan; Ji Hu; Haifeng Zhang; Jianfeng He; Zhengbing Han; Xufeng Yang; Cai Zhang; Gaojing Fan; Haisheng Zhang (Science of The Total Environment, 2024)

Tectonic deformation and kinematics of fluvial terraces marking the northeastern margin of the Tibetan Plateau - Zijuan Dong; Baotian Pan; Zhenbo Hu; David Bridgland; Jun Wang; Rob Westaway; Menghao Li; Qinhong Mo; Xiaohua Li; Xilin Cao; Meiling Zhong; Renzhe Pan (Quaternary Science Reviews, 2024)

Comparing evaporation from water balance framework and multiple models on a global scale - Jinghua Xiong; Abhishek; Chong Zhang; Li Xu; Hrishikesh A. Chandanpurkar; James S. Famiglietti; Pat J.-F. Yeh; Zhongbo Yu; Ningpeng Dong; Haoran Hao; Shuang Yi; Lei Cheng; et al. (Journal of Hydrology, 2024)

Sustainable Cr(VI) reduction in a membrane-less TPBC-MFC driven by solid watermelon rind - Yunlong Yang; Jinkui Zhang; Sijia Dong; Minjie Li; Pan Yang; Heng Meng; Jibo Xiao (Journal of Environmental Management, 2024)

Flexible multifunctional composite films for adjustable EMI shielding behavior under self-fixed deformation - Yang Bai; Jiayi Ju; Yujie Pan; Boyuan Zhang; Dong Wang; Xuchao Li (Chemical Engineering Journal, 2024)

Hydrodeoxygenation of guaiacol over modified coconut carbon supported Ni nanoparticles catalysts under alkaline condition - Yacong Deng; Yanlin Xu; Zhuoyi Liu; Wenhong Wang; Bin Liu; Hailing Guo; Yanpeng Li; Bin Dong; Yichuan Li; Yuan Pan; Yongming Chai; Chenguang Liu (Biomass and Bioenergy, 2024)

Versatile and efficient mammalian genome editing with Type I-C CRISPR System of Desulfovibrio vulgaris - Pan Li; Dingcai Dong; Fei Gao; Yuyang Xie; Honglin Huang; Siwei Sun; Zhao Ma; Cheng He; Jinsheng Lai; Xuguang Du; Sen Wu (Science China Life Sciences, 2024)

Factors controlling the phytoplankton crops, taxonomic composition, and particulate organic carbon stocks in the Cosmonaut Sea, East Antarctica - Yuhong Li; Jun Zhao; Dong Li; Jianming Pan; Jianfeng He; Ji Hu; Peisong Yu; Cai Zhang; Xufeng Yang; Haifeng Zhang; Zhengbing Han; Haisheng Zhang (Journal of Oceanology and Limnology, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Predicting tremor improvement after MRgFUS thalamotomy in essential tremor from preoperative spontaneous brain activity: A machine learning approach - Dong Zhang; Yongqin Xiong; Haoxuan Lu; Caohui Duan; Jiayu Huang; Yan Li; Xiangbing Bian; Dekang Zhang; Jiayou Zhou; Longsheng Pan; Xin Lou (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Manufacturing of Fe/C micro-electrolysis materials with the pyrite cinder towards the degradation of high-concentration organic wastewater - Tao Dong; Zhengqi Guo; Deqing Zhu; Jian Pan; Wenzhuo Ma; Siwei Li; Yue Shi (Journal of Environmental Chemical Engineering, 2024)

Performance study of activated multi-walled carbon nanotubes on catalyzing amine-based carbon capture - Lingling Li; Xin He; Pan Li; Si Chen; Tongtong Wang; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2024)

Testosterone-promoting effects of Trichosanthes kirilowii-derived peptides on TM3 cells - Zhilin He; Dong Peng; Jieyu Zeng; Wanying Liang; Xinqi Li; Junyi Chen; Pan Li; Bing Du; Hua Li (Food Bioscience, 2024)

Seismic behaviors of steel-FRP composite bar-reinforced engineered cementitious composites columns under reversed cyclic loads - Li Xu; Xiaoyi Wang; Bingqing Dong; Xiao Yang; Jinlong Pan (Engineering Structures, 2024)

Facilely prepare ultra-high molecular weight polypropylene loose nanofiltration membrane for efficient dye/salt separation - Wenqiang Gai; Shaoao Hu; Zhuoqun Li; Guangshun Dong; Xinyu Pan; Cuncheng Li; Shanshan Xu; Jian Pan (Desalination, 2024)

Preparation of presulfided oil-soluble NiMo catalyst for slurry bed hydrocracking of vacuum residue - Bin Liu; Hongyang Lv; Xingxing Cui; Guangzheng Sun; Xu Zhang; Bin Dong; Yichuan Li; Yuan Pan; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2024)

Amino polycarboxylic acid complex agent modified Fe0 enhanced activation of H2O2 double decomposition pathways for tetracycline removal under neutral condition - Zhujun Dong; Zhutong Dong; Yuzhu Xue; Haiying Lu; Minyi Yu; Yao Duan; Xiaoyu Li; Zihao Li; Wenyan Zhang; Gengbo Ren; Chen Chen; Xiang Li; et al. (Chemical Engineering Journal, 2024)

Realizing enhanced energy storage performance of Na0.47Bi0.47Ba0.06TiO3-based relaxors with weak coupling behavior by manipulating phase fraction - Yue Pan; Qinpeng Dong; Jiangping Huang; Xiuli Chen; Xu Li; Huanfu Zhou (Chemical Engineering Journal, 2024)

Novel furan-containing linear polymer with strong built-in electric field for H2O2 photosynthesis - Yingxin Guo; Feiyang Yu; Yuming Dong; Xiangguang Li; Tiwei He; Zenan Li; Chengsi Pan; Hui Zhao; Guangli Wang; Zhenhui Kang; Yongfa Zhu; Junshan Li (Chemical Engineering Journal, 2024)

SOX9 Promotes Collagen VI Secretion by Upregulating PCOLCE in Neurofibroma - Xuan Yao; Bo Wang; Yuanping Su; Zhitong Bing; Qiao Li; Qiang Dong; Hang Yin; Jianying Wang; Yawen Pan; Guoqiang Yuan (Molecular Neurobiology, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

A novel solar flare forecast model with deep convolution neural network and one-against-rest approach - Shunhuang Zhang; Yanfang Zheng; Xuebao Li; Hongwei Ye; Liang Dong; Xusheng Huang; Pengchao Yan; Xuefeng Li; Jinfang Wei; Changtian Xiang; Xiaotian Wang; Yexin Pan (Advances in Space Research, 2024)

A rotated rice spike detection model and a crop yield estimation application based on UAV images - Yunting Liang; Huifen Li; Han Wu; Yinwei Zhao; Zhijie Liu; Dong Liu; Zongru Liu; Gangao Fan; Zhaoyang Pan; Zhuo Shen; Jia Lv; Jiyu Li (Computers and Electronics in Agriculture, 2024)

Impacts of rapidly urbanizing watershed comprehensive management on per- and polyfluoroalkyl substances pollution: Based on PFAS “diversity” assessment - Nan Xu; Zhile Pan; Wenjing Guo; Shaoyang Li; Dianbao Li; Yanran Dong; Weiling Sun (Water Research, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Bensulfuron methyl induced multiple stress responses in the field wheat plants: Microbial community and metabolic network disturbance - Chunran Zhou; Dong Li; Peijuan Miao; Haiyan Cheng; Hui Zhang; Xiaoying Wan; Huan Yu; Yujiao Jia; Qinyong Dong; Canping Pan (Journal of Hazardous Materials, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

ALCSF: An adaptive and anti-noise filtering method for extracting ground and top of canopy from ICESat-2 LiDAR data along single tracks - Bingtao Chang; Hao Xiong; Yuan Li; Dong Pan; Xiaodong Cui; Wuming Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Changes of intestinal barrier in the process of intestinal inflammation induced by Aeromonas hydrophila in snakehead (Channa argus) - Xue-qin Wu; Xiu-mei Chen; Yi-yu Pan; Chuang Sun; Jia-xin Tian; Ai-dong Qian; Xiao-tian Niu; Yi-di Kong; Min Li; Gui-qin Wang (Fish & Shellfish Immunology, 2024)

Development and validation of individualized tacrolimus dosing software for Chinese pediatric liver transplantation patients: a population pharmacokinetic approach - Siyu Yang; Jian Wei; Xueqiang Pan; Ze Li; Xuanling Zhang; Zhe Li; Xianzhe Dong; Zixin Hua; Xingang Li (European Journal of Clinical Pharmacology, 2024)

Conflict Dynamics of Post-Retrieval Extinction: A Comparative Analysis of Unconditional and Conditional Reminders Using Skin Conductance Responses and EEG - Dong-ni Pan; Delhii Hoid; Oliver T. Wolf; Christian J. Merz; Xuebing Li (Brain Topography, 2024)

Nutrition and feeds for abalone: Current knowledge and future directions - Xinxin Li; Dong Huang; Mingzhu Pan; Javad Sahandi; Zhenhua Wu; Kangsen Mai; Wenbing Zhang (Reviews in Aquaculture, 2024)
Abalone is a commercially important mariculture mollusc because of its nutrient‐rich value and extensive market demand. To date, over 95% of the abalone supply has been contributed by farming. Macroalgae are the natural food of abalones. However, the supply of macroalgae is unstable owing to seasonal restrictions. This limits the success of abalone farming. Therefore, formulated diets are crucial for the ongoing expansion and sustainable development of abalone culture. The most important considerations in formulated diets are the nutrient composition and commercially available feed ingredients. This review presents a comprehensive description of the nutrient requirements of abalones and the role that nutrients play in regulating abalone growth and health. The dietary proteins, lipids, carbohydrates, macroalgae sources and feed additives currently used in abalone feeds were subsequently summarised. Additionally, this review also highlights the importance of prioritizing the development of sustainable alternative sources of proteins, carbohydrates and macroalgae to meet the increasing demand for abalone feed. Based on the information provided, future directions in the knowledge of abalone nutrition and feeds are subsequently discussed, which will guide further research towards the development of well‐balanced commercial feeds that enhance feed utilisation and promote abalone growth and health.

Response of microbial communities and biogeochemical cycling functions to sediment physicochemical properties and microplastic pollution under damming and water diversion projects - Xiong Pan; Li Lin; Xiaohuan Cao; Zheng Jing; Lei Dong; Wenliang Zhai (Science of The Total Environment, 2024)

Comprehensive analyses show the enhancement effect of exogenous melatonin on fluroxypyr-meptyl multiple phase metabolisms in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Si Ying Li; Ya Nan Qu; Gan Ai; Yan Hui Wang; Dong Jin Pan; Hao Wen Wang; Dan Lu; Xiao Liang Liu (Pesticide Biochemistry and Physiology, 2024)

Structural variations of a new fertility restorer gene, Rf20, underlie the restoration of wild abortive-type cytoplasmic male sterility in rice - Shufeng Song; Yixing Li; Mudan Qiu; Na Xu; Bin Li; Longhui Zhang; Lei Li; Weijun Chen; Jinglei Li; Tiankang Wang; Yingxin Qiu; Mengmeng Gong; et al. (Molecular Plant, 2024)

Protective effect of feed additive ferulic acid on respiratory depression and oxidation imbalance of carp induced by pesticide difenoconazole via ROS/NF-κB/NLRP3 axis - Yannan Xiang; Mengxin Li; Enzhuang Pan; Ying Li; Weiping Yan; Yuanyuan Li; Guangquan Ji; Jingquan Dong (Fish & Shellfish Immunology, 2024)

Ultra-high-molecular weight cyclic olefin copolymers with excellent all-round performance prepared via highly effective quasi-living copolymerization - Dong Huang; Xu Lu; Kunyu Zhang; Yafei Wang; Fei Wang; Huan Gao; Yingli Ding; Li Pan; Yang Li; Yuesheng Li (Chemical Engineering Journal, 2024)

Performance activation mechanism of aluminum-based layered double hydroxides adsorbents for recovering Li+ by pH modulating - Yanle Li; Chunxi Hai; Junjie Huo; Wencheng Pan; Tiandong Chen; Xiang Li; Xin He; Yanxia Sun; Shengde Dong; Luxiang Ma; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2024)

Mechanism and simulation analysis of high electric field of NaNbO3 − based energy storage ceramics based on defect engineering design - Qinpeng Dong; Dafu Zeng; Yue Pan; Peng Nong; Xiuli Chen; Xu Li; Huanfu Zhou (Chemical Engineering Journal, 2024)

Downregulation of OATP2B1 by proinflammatory cytokines leads to 5-ASA hyposensitivity in Ulcerative colitis - Ping Li; Jun Luo; Yiming Jiang; Xiaoyi Pan; Minlei Dong; Binxin Chen; Jinhai Wang; Hui Zhou; Huidi Jiang; Yangri Duan; Nengming Lin (Chemico-Biological Interactions, 2024)

The impact of co-exposure to polystyrene microplastics and norethindrone on gill histology, antioxidant capacity, reproductive system, and gut microbiota in zebrafish (Danio rerio) - Shuhui Zhou; Hongjie Lin; Ziyun Liu; Xiaoyi Lian; Chang-Gui Pan; Zhongdian Dong; Zhong Lin; Chengyong Li; Liping Hou; Yan-Qiu Liang (Aquatic Toxicology, 2024)

Metagenomic Next-Generation Sequencing as an Effective Diagnostic Tool for Talaromycosis in HIV-Negative Patients - Li Jiang; Tian-wei Liang; Najwa Al-Odaini; Yuan Hu; Minli Huang; Lili Wei; Xiu-ying Li; Kai-su Pan; Dong-yan Zheng; Zhi-wen Jiang; Gao Wei; Cun-wei Cao (Mycopathologia, 2024)

A novel approach for estimating fractional cover of crops by correcting angular effect using radiative transfer models and UAV multi-angular spectral data - Yuanyuan Pan; Wenxuan Wu; Jiaoyang He; Jie Zhu; Xi Su; Wanyu Li; Dong Li; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Computers and Electronics in Agriculture, 2024)

Association between ambient air pollution and dry eye symptoms among Chinese individuals during the COVID-19 pandemic: A national-based study - Jia-Yan Kai; Yi-Bo Wu; Xing-Xuan Dong; Yi-Fan Miao; Dan-Lin Li; Dan-Ning Hu; Carla Lanca; Andrzej Grzybowski; Chen-Wei Pan (Science of The Total Environment, 2024)

Triterpenoids from the leaves of Eleutherococcus sessiliflorus, and their antiproliferative activities in TNF-α induced HFLS-RA cells - Yan Liu; Yuqing Wang; Peng Jiang; Dong Han; Jiatong Wu; Siyi Wang; Haidan Zou; Yikai Jiang; Xiaomao Li; Juan Pan; Zhichao Hao; Wei Guan; et al. (Phytochemistry, 2024)

Integrative omics analyses of tea (Camellia sinensis) under glufosinate stress reveal defense mechanisms: A trade-off with flavor loss - Huan Yu; Dong Li; Yangliu Wu; Peijuan Miao; Chunran Zhou; Haiyan Cheng; Qinyong Dong; Yingjie Zhao; Zhusheng Liu; Li Zhou; Canping Pan (Journal of Hazardous Materials, 2024)

Novel a-linolenic acid emulsions stabilized by octenyl succinylated starch -soy protein-epigallocatechin-3-gallate complexes: Characterization and antioxidant analysis - Tenglong Geng; Lidan Pan; Xiaorui Liu; Die Dong; Bo Cui; Li Guo; Chao Yuan; Meng Zhao; Haibo Zhao (Food Chemistry, 2024)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Active landslide detection using integrated remote sensing technologies for a wide region and multiple stages: A case study in southwestern China - Huiyan Lu; Weile Li; Qiang Xu; Wenlong Yu; Shengsen Zhou; Zhigang Li; Weiwei Zhan; Weimin Li; Shanmiao Xu; Pan Zhang; Xiujun Dong; Jingtao Liang; et al. (Science of The Total Environment, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

A comparative evaluation of the structure, functionality and volatile profiles of Trichosanthes kirilowii seed protein isolates based on different extraction methods - Dong Peng; Zhilin He; Xiangmin Pan; Rui Zheng; Hanxiao Bao; Jingru Liao; Ling Dong; Weiwen Li; Jianping Chen; Pan Li; Bing Du (Food Chemistry, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Protopanaxadiol improves lupus nephritis by regulating the PTX3/MAPK/ERK1/2 pathway - Zhenyuan Li; Hailin Gan; Kai Ji; Mingyan Yang; Tao Pan; Xiangting Meng; Teng Liu; Zhixia Wang; Baifang Gong; Ke Liu; Dong Qi; Huaying Fan (Journal of Natural Medicines, 2024)

Evaluation of Opaque-2 effects on popping characteristics using iTRAQ-based proteome profiles in popcorn - Yongbin Dong; Qi Zheng; Junjie Zhu; Qingling Shi; Siqi Jiang; Mengying Pan; Xinyue Zhang; Long Zhang; Yuling Li (Euphytica, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Mechanisms for improving the quality of crucian carp (Carassius auratus) by short-term low-salinity treatment revealed by UPLC-MS and GC–MS - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture International, 2024)

Effects of salinity on the growth, physiological and biochemical components of microalga Euchlorocystis marina - Yao Pan; David Kwame Amenorfenyo; Mingbiao Dong; Ning Zhang; Xianghu Huang; Changling Li; Feng Li (Frontiers in Marine Science, 2024)
Euchlorocystis marina , a new marine species of the genus Euchlorocystis discovered in 2022, has the potential to improve the water quality in mariculture ponds. However, the effects of salinity on the growth, physiology, and biochemical composition of these algae are not well understood. In this study, changes in physiological and biochemical indices such as cell density, photosynthetic pigment, polysaccharide, and lipid content of E. marina under different salinity treatments were analyzed. The results showed that the highest cell density was observed at a salinity of 15‰. The lowest photosynthetic pigment content was observed at a salinity of 60‰, and the highest polysaccharide and lipid content was observed at a salinity of 60‰. These results indicated that lower salinity was more conducive to E. marina reproduction and growth. E. marina can accumulate polysaccharides and lipids in high salinity environments. This study provides new information for understanding the salinity adaptation strategies of E. marina and has practical significance for its development and utilization.

Natural versus artificial seawater: Impacts on antioxidant capacity, muscle quality and gut microbiota of Acanthopagrus schlegelii during temporary rearing - Yunyun Pan; Chang Liu; Yawen Hong; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture, 2024)

Stomatohabitans albus gen. nov., sp. nov., an oral living facultative anaerobic actinobacteria isolated form Steller sea lion, and proposal of Stomatohabitantaceae fam. nov. and Stomatohabitantales ord. nov - Zi-Wen Yang; Wen-Li Liu; Peng Zhang; Dan-Yuan Guo; Hong-Chuan Wang; Jia-Ling Li; Pan-Deng Wang; Gui-Xin Dong; Guo-Xing Nie; Wen-Jun Li (Systematic and Applied Microbiology, 2024)

Anticyanobacterial effect of p-coumaric acid on Limnothrix sp. determined by proteomic and metabolomic analysis - Lingzhi Li; Gengxin Xie; Pan Dong; Hui Tang; Liping Wu; Liang Zhang (Science of The Total Environment, 2024)

Oxidation of iso-propylbenzene at elevated pressure and the development of a comprehensive model - Zhi-Hao Jin; Dong-Xu Tian; Guan-Fu Pan; Jin-Tao Chen; Wang Li; Zhen-Yu Tian (Fuel, 2024)

The onset of fluid-induced alteration of fluorapatite in iron oxide-apatite deposits: Insights from fluorapatite and their monazite inclusions at the Heiyingshan iron deposit, Beishan Metallogenic Belt, Northwest China - Yong Yin; Hao Hu; Xiao-Dong Deng; Daniel Harlov; Jian-Wei Li; Zhuang Duan; Zhe-Jian Pan; David R. Lentz (Chemical Geology, 2024)

The effects of climatic change and inter-annual variability on glacier retreat from ~ 1850s AD moraines in the Kuoqionggangri peak region, southern Tibetan Plateau - Xiangke Xu; Hongjie Zhang; Yaqing Sun; Baiqing Xu; Jiule Li; Guocheng Dong; Baolin Pan (Climate Dynamics, 2024)

Opportunities and challenges of polyphenols and polysaccharides for type 1 diabetes intervention - Binbin Li; Li-Long Pan; Xiaohua Pan; Xiaoliang Dong; Zhengnan Ren; Hao Zhang; Wei Chen; Paul de Vos; Jia Sun (Critical Reviews in Food Science and Nutrition, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

RETRACTED: Response of C:N:P stoichiometry to long-term drainage of peatlands: Evidence from plant, soil, and enzyme - Shengzhong Wang; Yaoyao Du; Shasha Liu; Junxiao Pan; Fan Wu; Yingzhuo Wang; Yuting Wang; Hongkai Li; Yanmin Dong; Zucheng Wang; Ziping Liu; Guodong Wang; et al. (Science of The Total Environment, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Impact of tropical cyclones on the hydrodynamics and sediment dynamics of the radial sand ridge system in the southern Yellow Sea - Gang Yang; Chunhui Li; Yi Zhong; Xishan Pan; Chengyi Zhao; Changming Dong (Ocean Modelling, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

The effect of electron beam irradiation combined with slurry ice on physicochemical parameters and bacterial communities of shrimp (Litopenaeus vannamei) during refrigerated storage - Chang Liu; Yunyun Pan; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Control, 2024)

Rapid design for large-scale parallel CFRP cable with multi-source experimental data - Li Dong; Peng Feng; Chi Lu; Pan Zhang; Guozhen Ding (Engineering Structures, 2024)

Contrasting moist heat across local climate zones in heat and non-heat waves: Insights from 29 Chinese metropolises - Sida Jiang; Wenfeng Zhan; Long Li; Chunli Wang; Pan Dong; Shasha Wang; Yingying Ji; Fan Huang; Zihan Liu; Yihan Gao (Building and Environment, 2024)

Differential detection of H1N1 virus spiker proteins by two hexaphenylbutadiene isomers based on size-matching principle - Xiaoling Pan; Jian Wang; Kai Zhang; Peng Sun; Jianbing Shi; Junge Zhi; Zhengxu Cai; Zi Li; Dayan Wang; Bin Tong; Yuping Dong (Analytica Chimica Acta, 2024)

Investigation of the migration of natural organic matter-iron-antimony nano-colloids in acid mine drainage - Yuqin Zhang; Pan Wu; Jian Zhu; Peng Liao; Elias Niyuhire; Feifei Fan; Wenjian Mao; Lisha Dong; Ruyi Zheng; Yi Li (Science of The Total Environment, 2024)

Multivariate time series prediction for CO2 concentration and flowrate of flue gas from biomass-fired power plants - Shiyuan Pan; Xiaodan Shi; Beibei Dong; Jan Skvaril; Haoran Zhang; Yongtu Liang; Hailong Li (Fuel, 2024)

Synergistic effect between CoSx and MoS2 at the micrometer scale: Considerable promotion of the hydrodesulfurization of DBT - Fengyu Tian; Wenhong Wang; Bin Liu; Yuan Pan; Bin Dong; Yichuan Li; Yanpeng Li; Hailing Guo; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2024)

Frontogenesis and Frontolysis of a Cold Filament Driven by the Cross-Filament Wind and Wave Fields Simulated by a Large Eddy Simulation - Guojing Li; Dongxiao Wang; Changming Dong; Jiayi Pan; Yeqiang Shu; Zhenqiu Zhang (Advances in Atmospheric Sciences, 2024)

Immunoprotective effect of silybin through blocking p53-driven caspase-9-Apaf-1-Cyt c complex formation and immune dysfunction after difenoconazole exposure in carp spleen - Enzhuang Pan; Yue Xin; Xueqing Li; Kaixin Ping; Xing Li; Ying Sun; Xuhui Xu; Jingquan Dong (Environmental Science and Pollution Research, 2024)

Hierarchical processing enabled by 2D ferroelectric semiconductor transistor for low-power and high-efficiency AI vision system - Guangcheng Wu; Li Xiang; Wenqiang Wang; Chengdong Yao; Zeyi Yan; Cheng Zhang; Jiaxin Wu; Yong Liu; Biyuan Zheng; Huawei Liu; Chengwei Hu; Xingxia Sun; et al. (Science Bulletin, 2024)

Efficient treatment of alcohol wastewater and its potential pollutant control strategies - Heng Wu; Ruixiao Yan; Anjie Li; Dong Huang; Jiang Pan; Piao Zhao; Zhilin Xing (Journal of Water Process Engineering, 2024)

Highly efficient iodide adsorption from medical radioactive wastewater by strong alkaline anion exchange fiber - Zhihui Liao; Ning Pan; Jiale Liu; Chunyan Ma; Xue Xia; Jianju Deng; Guohui Yang; Xiaoan Li; Zhengguo Chen; Wencai Cheng; Wei Zhang; Xiaoqin Nie; et al. (Journal of Environmental Chemical Engineering, 2024)

Dimensional design of Fe0.9Co0.1 nano-alloys with enhanced low-frequency microwave absorption - Renchao Hu; Li Li; Xinwei Xu; Desheng Pan; Jiufeng Dong; Cheng Zhen; M. Danny Gu; Hong Wang (Chemical Engineering Journal, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Understanding the release, migration, and risk of heavy metals in coal gangue: An approach by combining experimental and computational investigations - Jihong Dong; Jiabang Li; Yu Huang; Jingyu Zhong; Kai Dun; Min Wu; Lijuan Zhang; Quan Chen; Bo Pan (Journal of Hazardous Materials, 2024)

Production of single cell protein rich in potassium by Nectaromyces rattus using biogas slurry and molasses - Yuanyuan Yi; Jiabao Li; Pan Zhou; Fenglin Jia; Yichao Chen; Dong Li (Journal of Environmental Management, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Efficient removal of endocrine disruptors using nano zero-valent iron loaded organo-attapulgite: Mechanism and factors - Lei Dong; Li Lin; Guochuan Yin; Yueqi Cao; Xiong Pan; Han Zheng; Hongwu Jiang; Weijie Wu (Chemical Engineering Journal, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

From feedstock to digestion: Unraveling the impact of humic acid composition on anaerobic digestion - Yeqing Li; Shasha Yu; Xingru Yang; Yijing Feng; Liming Dong; Yi Zhang; Lu Feng; Mahmoud Mazarji; Junting Pan (Science of The Total Environment, 2023)

Hydrodeoxygenation of guaiacol to bio-hydrocarbons in alkaline condition on the Ni/AC catalyst with an “acid-switch” - Yanlin Xu; Yacong Deng; Bin Liu; Zhuoyi Liu; Wenhong Wang; Yuan Pan; Bin Dong; Yichuan Li; Changlong Yin; Hailing Guo; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2023)

Development and External Validation of Nomogram for Cerebral Infarction in Moyamoya Diseases - Pan Chen; Ying Wang; Shifu Li; Dong Tang; Shuai Yang; Feiyue Zeng; Lebao Yu; Dong Zhang; Wei Ding; Shuihua Wu; Fenghua Chen; Zheng Huang (Translational Stroke Research, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Imidacloprid-induced stress affects the growth of pepper plants by disrupting rhizosphere-plant microbial and metabolite composition - Dong Li; Chunran Zhou; Shuai Wang; Zhan Hu; Jia Xie; Canping Pan; Ranfeng Sun (Science of The Total Environment, 2023)

Room-temperature orbit-transfer torque enabling van der Waals magnetoresistive memories - Zhen-Cun Pan; Dong Li; Xing-Guo Ye; Zheng Chen; Zhao-Hui Chen; An-Qi Wang; Mingliang Tian; Guangjie Yao; Kaihui Liu; Zhi-Min Liao (Science Bulletin, 2023)

Dynamics of chromophoric dissolved organic matter in a highly productive Amundsen Sea polynya - Ji Hu; Siyou Xue; Jun Zhao; Zhengbing Han; Dong Li; Haifeng Zhang; Peisong Yu; Minhui Zheng; Jianming Pan; Yongge Sun (Marine Chemistry, 2023)

Simple yet efficient downscaling of land surface temperatures by suitably integrating kernel- and fusion-based methods - Pan Dong; Wenfeng Zhan; Chenguang Wang; Sida Jiang; Huilin Du; Zihan Liu; Yangyi Chen; Long Li; Shasha Wang; Yingying Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Protein carbonylation and structural changes in porcine myofibrillar protein exposed to metal ion-H2O2-ascorbate and linoleic acid-lipoxidase oxidizing systems - Wenhui Wang; Xiaolei Jia; Chuanyu Guo; Jinfeng Pan; Xiuping Dong; Shengjie Li (Food Research International, 2023)

Numerical simulation and theoretical analysis on RECC ring beam joints for RECC-encased CFST composite columns - Bingqing Dong; Jinlong Pan; Li Xu (Engineering Structures, 2023)

Pseudomonas aeruginosa-induced mitochondrial dysfunction inhibits proinflammatory cytokine secretion and enhances cytotoxicity in mouse macrophages in a reactive oxygen species (ROS)-dependent way - Haitao Yang; Yan Wang; Hui Fan; Feixue Liu; Huimiao Feng; Xueqing Li; Mingyi Chu; Enzhuang Pan; Daoyang Teng; Huizhen Chen; Jingquan Dong (Journal of Zhejiang University-SCIENCE B, 2023)

The nonlinear relationship between air quality and housing prices by machine learning - Weiwen Zhang; Sheng Pan; Zhiyuan Li; Ziqing Li; Zhaoyingzi Dong (Environmental Science and Pollution Research, 2023)

Design, synthesis, and biological activity of 9- O -cinnamoylberberines as novel lipid-lowering agents - Yuan Kong; Qi-Qi Xing; Yu-Xuan Tian; Lin Li; Pan Yu; Lin-Guo Zhao; Dong-Dong Li (Natural Product Research, 2023)

Deformation Characteristics of Pipelines Due to Adjacent Excavation in Riprap Reclamation Strata - Xiaohua Bao; Chunxun Liu; Lijuan Li; Jun Shen; Jihao Pan; Qijun Dong; Xiangsheng Chen (Journal of Marine Science and Engineering, 2023)
The Shenzhen Ma Wan area has special geotechnical conditions, with more than 50% of the area being reclaimed rock formations. Riprap reclamation strata are particularly susceptible to significant deformation upon stress release. To comprehensively comprehend the reaction of existing pipelines to the excavation of an adjacent deep foundation pit within the riprap reclamation strata, an interaction of the soil–pipeline was conducted by encompassing both scaled model tests and numerical simulations based on a cross-sea channel project. Firstly, scaled model tests were performed on a soil–pipeline interaction caused by excavation. Subsequently, the numerical model was verified by comparing the numerical simulation results with the scaled model test results. Then, the internal force, strain of the pipeline, and soil surface deformation under the conditions of a soil layer with riprap were analyzed, and the results were compared with the case without riprap. Finally, the influence of the support structures was analyzed. The results indicated that the presence of the riprap in strata led to a 19% increase in vertical displacement of the ground surface and a 35% increase in the pipeline bending moment compared with the case without riprap in the same strata. The maximum internal force and strain occurred at an inclined angle of 45° in the pipeline section. Furthermore, it was found that the first lateral support after excavation played a pivotal role in controlling the overall deformation of the foundation pit. The changes in stiffness in the lateral support were more sensitive to the horizontal displacement than the vertical displacement of the pipeline. The results provide valuable insights for the design and safety evaluation of engineering projects in riprap reclamation strata.

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Exogenous nanoselenium alleviates imidacloprid-induced oxidative stress toxicity by improving phenylpropanoid metabolism and antioxidant defense system in Perilla frutescens (L.) Britt - Qinyong Dong; Dong Li; Yangliu Wu; Chunran Zhou; Yongxi Lin; Peijuan Miao; Jiaqi Li; Canping Pan (Journal of Plant Physiology, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Antarctic krill (Euphausia superba) oil high internal phase emulsions improved the lipid quality and gel properties of surimi gel - Yinyin Lv; Xiaosong Sun; Hui Jia; Ruoyi Hao; Mráz Jan; Xianbing Xu; Shengjie Li; Xiuping Dong; Jinfeng Pan (Food Chemistry, 2023)

System identification of excited beam immersed in granular materials: A multifrequency data-based method in a variational framework - Jinlu Dong; Zhenhua Niu; Jian Li; Guangyang Hong; Jingwu Pan; Hang Li (Engineering Structures, 2023)

Highly active Ag/ZnO/ZnAl-LDH heterojunction photocatalysts for NO removal - Hongyi Tang; Xiao'ai Luo; Wenting Li; Yue Pan; Siqi Wang; Hao Ma; Yu Shen; Ruimei Fang; Fan Dong (Chemical Engineering Journal, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Ameliorative effects of silybin against avermectin-triggered carp spleen mitochondrial dysfunction and apoptosis through inhibition of PERK-ATF4-CHOP signaling pathway - En-Zhuang Pan; Yue Xin; Xue-Qing Li; Xin-Yu Wu; Xue-Lian Tan; Jing-Quan Dong (Fish Physiology and Biochemistry, 2023)

Disruption of the intestinal barrier by avermectin in carp involves oxidative stress and apoptosis and leads to intestinal inflammation - Hairui Han; Nana He; Enzhuang Pan; Xuelian Tan; Zuwang Yang; Xueqing Li; Dahua Shi; Jingquan Dong (Pesticide Biochemistry and Physiology, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Allelopathy of p-coumaric acid on Limnothrix sp., a bloom-forming cyanobacteria - Liping Wu; Lingzhi Li; Pan Dong; Liang Zhang; Hui Tang; Ya Han; Gengxin Xie (Algal Research, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Prolonged fluoride exposure induces spatial-memory deficit and hippocampal dysfunction by inhibiting small heat shock protein 22 in mice - Jinge Xin; Bin Zhu; Hesong Wang; Yong Zhang; Ning Sun; Xi Cao; Liqin Zheng; Yanxi Zhou; Jing Fang; Bo Jing; Kangcheng Pan; Yan Zeng; et al. (Journal of Hazardous Materials, 2023)

Dual-crosslinking network and pre-anchorage effect enable high-performance, low-cost, and eco-friendly geopolymer adhesive for the wood industry - Dawei Pan; Na Zhang; Senchi Li; Meihan Dong; Zhiming Yu; Bo Zhang; Yang Zhang (Journal of Cleaner Production, 2023)

CaCl2 treatment effectively delays postharvest senescence of passion fruit - Huagen Xu; Pei Qiao; Jiali Pan; Ziyi Qin; Xia Li; Hock Eng Khoo; Xinhong Dong (Food Chemistry, 2023)

Regional distribution and migration potential of antibiotic resistance genes in croplands of Qinghai Tibet Plateau - Dagang Song; Xue Tang; Akash Tariq; Kaiwen Pan; Dong Li (Environmental Research, 2023)

Effects of choline supplementation on growth performance, liver histology, nonspecific immunity and related genes expression of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) fed with high-lipid diets - Tao Li; Xiaobo Yan; Xiaohui Dong; Simiao Pan; Beiping Tan; Shuang Zhang; Xiangxiang Suo; Weibin Huang; Menglong Zhou; Yuanzhi Yang (Fish & Shellfish Immunology, 2023)

Iodine nanotrap for highly efficient iodine capture under high temperature - Feng Shui; Qiong Lei; Xinglong Dong; Tingting Pan; Zhiyuan Zhang; Jinli Li; Mao Yi; Laiyu Zhang; Xiongli Liu; Zifeng You; Shiqi Yang; Rufeng Yang; et al. (Chemical Engineering Journal, 2023)

Scutellarin prevents acute alcohol-induced liver injury via inhibiting oxidative stress by regulating the Nrf2/HO-1 pathway and inhibiting inflammation by regulating the AKT, p38 MAPK/NF-κB pathways - Xiao Zhang; Zhicheng Dong; Hui Fan; Qiankun Yang; Guili Yu; Enzhuang Pan; Nana He; Xueqing Li; Panpan Zhao; Mian Fu; Jingquan Dong (Journal of Zhejiang University-SCIENCE B, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Simultaneous identification of groundwater contaminant source and hydraulic parameters based on multilayer perceptron and flying foxes optimization - Yidan Li; Wenxi Lu; Zidong Pan; Zibo Wang; Guangqi Dong (Environmental Science and Pollution Research, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

Enhance the stability of oxygen vacancies in SrTiO3 via metallic Ag modification for efficient and durable photocatalytic NO abatement - Hao Ma; Wenjia Yang; Hongyi Tang; Yue Pan; Wenting Li; Ruimei Fang; Yu Shen; Fan Dong (Journal of Hazardous Materials, 2023)

Impact of side-chain engineering on quantum efficiency and voltage losses in organic solar cells - Jing Wang; Deping Qian; Fangliang Dong; Hongbo Wu; Hailin Pan; Shijie Liang; Hanyu Wu; Xunda Feng; Weiwei Li; Ming Wang; Zheng Tang; Zaifei Ma (Chemical Engineering Journal, 2023)

Effects of Antimicrobial Peptides Gal-13 on the Growth Performance, Intestinal Microbiota, Digestive Enzyme Activities, Intestinal Morphology, Antioxidative Activities, and Immunity of Broilers - Yufei Wang; Jianzhen Li; Xixi Dai; Zhenhua Wang; Xueqin Ni; Dong Zeng; Yan Zeng; Dongmei Zhang; Kangcheng Pan (Probiotics and Antimicrobial Proteins, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Establishment of Agrobacterium-mediated transformation system to Juglans sigillata Dode ‘Qianhe-7’ - Rong Wei; Wen’e Zhang; Chunxiang Li; Zhenkun Hao; Dong Huang; Wenlong Zhang; Xuejun Pan (Transgenic Research, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Responses of the Sea Surface Temperature and Suspended Matter Concentration to ENSO Events in the Bohai Sea - Xue Liu; Dong Ding; Guangxue Li; Yang Zhang; Shidong Liu; Nan Wang; Yi Zhong; Xue Yang; Yufeng Pan; Di Yu; Lei Zhang; Wenjing Xue (Journal of Ocean University of China, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Social and paternal female choice for male MHC genes in golden snub‐nosed monkeys ( Rhinopithecus roxellana ) - Pei Zhang; Bingyi Zhang; Derek W. Dunn; Xiaoyue Song; Kang Huang; Shixuan Dong; Fei Niu; Meijing Ying; Yingying Zhang; Yixin Shang; Ruliang Pan; Baoguo Li (Molecular Ecology, 2023)
Genes of the major histocompatibility complex (MHC) play important roles in vertebrate immunocompetence. MHC genes thus offer females indirect benefits to mate choice through the production of offspring of an optimal MHC genotype. Females may choose males with specific MHC haplotypes, dissimilar MHC genotypes, MHC heterozygous males or MHC‐diverse males. We tested these four alternatives for both female social and paternal choice in wild golden snub‐nosed monkeys ( Rhinopithecus roxellana ) by examining overall genetic variability (via microsatellites) and four MHC‐genes ( DRB1 , DRB2 , DQA1 and DQB1 ). Monte Carlo randomization tests showed that MHC dissimilarity was favoured for social choice (males to which females were socially affiliated) and intermediate MHC dissimilarity was favoured in paternal choice (fathers of offspring). No evidence of inbreeding avoidance was found for either social or paternal mates. We found that MHC heterozygotes, higher microsatellite multilocus heterozygosity and higher microsatellites diversity were favoured for social mates, and higher microsatellite diversity was favoured for paternal mates. Independent of male age, we found that the formation of male–female social pairings is significantly predicted by compatibility based on the sharing of MHC haplotypes. However, we found no evidence of independent genetic effects on the duration of male–female social pairings, male social status (achieving OMU leader male status or not), the number of females with which individual leader males paired, the likelihood of potential male–female pairings producing offspring, or whether males fathered offspring or not. Overall, our findings suggest different genetic factors are involved in social and paternal choice in R. roxellana .

Cereal polyphenols inhibition mechanisms on advanced glycation end products and regulation on type 2 diabetes - Lezhen Dong; Ying Li; Qin Chen; Yahui Liu; Zufang Wu; Daodong Pan; Ning Yan; Lianliang Liu (Critical Reviews in Food Science and Nutrition, 2023)

Protein kinase C is required for the pathogenicity of Setosphaeria turcica on maize - Pan Li; Hehe Sun; Jingao Dong; Zhimin Hao (Journal of Plant Pathology, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Shift of phytoplankton and microbial communities cause seasonal dynamics of odor compounds in Oncorhynchus mykiss cultured in a freshwater reservoir - Shuting Li; Fayi Wei; Xuan Dong; Miaojun Pan; Li Li; Xiangli Tian; Qinfeng Gao; Alan E. Wilson (Aquaculture, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Photodegradation behavior and mechanism of dibutyl phthalate in water under flood discharge atomization - Li Lin; Sheng Zhang; Lei Dong; Yueqi Cao; Wei Zhang; Xiong Pan; Yi Li; Chi Zhang; Jingxiang Tao; Di Jia; John Crittenden (Science of The Total Environment, 2023)

Integrated intelligent tactile system for a humanoid robot - Rongrong Bao; Juan Tao; Jing Zhao; Ming Dong; Jing Li; Caofeng Pan (Science Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Anthropogenic impacts on the nitrate pollution in an urban river: Insights from a combination of natural-abundance and paired isotopes - Wenjing Guo; Dong Zhang; Wenshi Zhang; Shen Li; Ke Pan; Hao Jiang; Quanfa Zhang (Journal of Environmental Management, 2023)

The performance and mechanism of CO2 desorption and corrosion in N-methyldiethanolamine aqueous solutions blended with amino acid ionic liquids - Mengying Li; Pan Zhang; Gongda Chen; Dong Fu (International Journal of Greenhouse Gas Control, 2023)

Inactivation of Microcystis aeruginosa by H2O2 generated from a carbon black polytetrafluoroethylene gas diffusion electrode in electrolysis by low-amperage electric current - Yuting Zhang; Li Lin; Di Jia; Lei Dong; Xiong Pan; Min Liu; Huawei Huang; Yuan Hu; John C. Crittenden (Environmental Pollution, 2023)

Triassic igneous activities in the east flank of the East Kunlun orogenic belt: the Daheba complex example - Nan Tian; Feng-Yue Sun; Zhong-Cui Pan; Liang Li; Yan Gu; Dong-Qian Wu; Jia-Fang Deng; Zhe-Dong Liu; Li Wang; Ya-Jing Zhang (International Geology Review, 2023)

Nanonitrator: novel enhancer of inorganic nitrate’s protective effects, predicated on swarm learning approach - Wen Pan; Geng Hu; Shaorong Li; Guoqing Li; Xiaoyu Feng; Zhifang Wu; Dong Zhang; Lizheng Qin; Xue Wang; Liang Hu; Junji Xu; Lei Hu; et al. (Science Bulletin, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Mechanisms regarding respiratory toxicity triggered by accumulation of ROS in carp exposed to difenoconazole - Huimiao Feng; Huizhen Chen; Jingchao Qiang; Baoshi Xu; Xinyu Wu; Enzhuang Pan; Haitao Yang; Xueqing Li; Jian Zhang; Jingquan Dong (Pesticide Biochemistry and Physiology, 2023)

Insights into characteristics of white rot fungus during environmental plastics adhesion and degradation mechanism of plastics - Feiyan Wu; Zhi Guo; Kangping Cui; Dazhuang Dong; Xue Yang; Jie Li; Zhangzhen Wu; Lele Li; Yaodan Dai; Tao Pan (Journal of Hazardous Materials, 2023)

Extraction of a perovskite from red mud and its photocatalytic reduction of CO2 - Siwei Li; Wei Liu; Deqinq Zhu; Jian Pan; Zhengqi Guo; Congcong Yang; Tao Dong; Shenghu Lu (Journal of Environmental Chemical Engineering, 2023)

Hydrophilic colloids (Konjac gum/Xanthan gum) in 3D printing of transitional food from fish paste - Xiliang Yu; Yue Wang; Wenyu Zhao; Shouwei Li; Jinfeng Pan; Sangeeta Prakash; Xiuping Dong (Food Hydrocolloids, 2023)

Effects of fabrication of conjugates between different polyphenols and bovine bone proteins on their structural and functional properties - Li Pan; Jingya Chen; Huihui Fu; Niannian Wang; Junrong Zhou; Shuyao Zhang; Shiling Lu; Juan Dong; Qingling Wang; Haiyan Yan (Food Bioscience, 2023)

Low content of highly reactive iron in sediments from Prydz Bay and the adjacent Southern Ocean: Controlling factors and implications for sedimentary organic carbon preservation - Wenhao Huang; Xiaoze Guo; Jun Zhao; Dong Li; Ji Hu; Haifeng Zhang; Cai Zhang; Zhengbing Han; Weiping Sun; Yongge Sun; Jianming Pan (Frontiers in Marine Science, 2023)
Examining iron (Fe) speciation in marine sediments is critical to understand Fe and carbon biogeochemical cycling in polar regions. In this study, we investigated the speciation of Fe in sediments from Prydz Bay and the adjacent Southern Ocean, and examined the factors controlling Fe speciation and its relationship with total organic carbon (TOC). Our results reveal that unreactive silicate Fe (Fe U ) is the dominant pool of total Fe (Fe T ), followed by poorly reactive sheet silicate Fe (Fe PRS ), reducible crystalline Fe oxides (Fe ox2 ), easily reducible amorphous/poorly crystalline Fe oxides (Fe ox1 ), and magnetite (Fe mag ), with carbonate-associated ferrous Fe (Fe carb ) being the smallest pool. The highly reactive Fe (Fe HR )/Fe T ratios (0.13 ± 0.06) in our study area are among the lowest end-member globally, primarily due to weak bedrock weathering and slow glacier melting. The Fe ox1 /Fe T ratios are similar to those in continental shelf and marginal seas containing highly weathered materials, while the Fe ox2 /Fe T ratios are significantly lower. This result implicates that low temperature inhibits the aging of iceberg melting-sourced Fe ox1 potentially, and accordingly the regulation of weathering on the Fe HR /Fe T ratio is mainly reflected in Fe ox2 /Fe T ratio. There are no significant correlations between TOC and Fe HR , Fe carb , Fe ox1 or Fe ox2 in the research region. Four distinct patterns of TOC/Fe HR ratio can be discerned by summarizing the global data set: (a) high TOC/Fe HR ratios (> 2.5) are likely the result of high marine primary productivity and low chemically weathered source materials; (b) low TOC/Fe HR ratios (< 0.6) are caused by high rates of Fe HR inputs and OC remineralization; (c) mid-range TOC/Fe HR ratios (0.6 – 2.5) typical of most river particulates and marginal sea sediments indicate the same Fe HR and OC sources and/or interactions between each other; (d) both low TOC and Fe HR content is the result of low marine primary productivity and weak chemical weathering. Our findings provide new insights into the relationship between Fe HR and TOC in polar sediments.

Rat tight junction proteins are disrupted after subchronic exposure to okadaic acid - Lu Huang; Bo Liu; Xiao-Wen Yu; Guang-Qiang Pan; Jia-Yi Xu; Dong Yan; Ya-Li Wang; Qiao-Nan Guo (Environmental Science and Pollution Research, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Immobilize Nd2O3 as simulated nuclear waste in silicate-apatite glass-ceramics - Yanrong Cheng; Xiaoyan Shu; Mingfen Wen; Yuexiang Lu; Pan Tan; Xirui Lu; Lingshuang Li; Faqin Dong (Process Safety and Environmental Protection, 2023)

Study on the thrust fluctuation and vortices of a pump-jet propulsor under different duct parameters - Han Li; Qiaogao Huang; Guang Pan; Xinguo Dong; Lianghao Xu (Ocean Engineering, 2023)

Characterization and catalytic mechanism of a direct demethylsulfide hydrolase for catabolism of the methylthiol-s-triazine prometryn - Jun Tang; Jinjin Yao; Dandan Pan; Junwei Huang; Jie Wang; Qing X. Li; Fengshou Dong; Xiangwei Wu (Journal of Hazardous Materials, 2023)

Sequential combination of pre-chlorination and powdered activated carbon adsorption on iodine removal and I-THMs control in drinking water - Renjie Pan; Yi-Li Lin; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Chemosphere, 2023)

China’s agricultural machinery operation big data system - Caicong Wu; Dong Li; Xiaoqiang Zhang; Jiawen Pan; Lei Quan; Lili Yang; Weizhong Yang; Qin Ma; Chunhua Su; Weixin Zhai (Computers and Electronics in Agriculture, 2023)

Comprehensive evaluation of novel fungicide benzovindiflupyr at the enantiomeric level: Bioactivity, toxicity, mechanism, and dissipation behavior - Xiaokang An; Xinglu Pan; Runan Li; Fengshou Dong; Wentao Zhu; Jun Xu; Xiaohu Wu; Yongquan Zheng (Science of The Total Environment, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Rapid elimination of butralin residues on tobacco, in water and soils by newly isolated Bacillus sp. LY05 - Qiuping Wang; Jiaohong Li; Rongyu Li; Xinglu Pan; Fengshou Dong; Xiaomao Wu (Journal of Environmental Chemical Engineering, 2023)

Synergistic engineering of electronic structure and particle size in SnSe@CNF anode toward high performance potassium ion batteries - Naiqing Ren; Lifeng Wang; Jiemin Dong; Kuo Cao; Yixuan Li; Fei Chen; Jingchao Xiao; Bicai Pan; Chunhua Chen (Chemical Engineering Journal, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

Spatial-temporal variations of short-lived mesoscale eddies and their environmental effects - Shidong Liu; Jishang Xu; Lulu Qiao; Guangxue Li; Jinghao Shi; Dong Ding; Di Yu; Xue Yang; Yufeng Pan; Siyu Liu; Xiaoshuang Fu (Frontiers in Marine Science, 2023)
Mesoscale eddies (MEs) affect the transport and redistribution of oceanic matter and energy. The long-lived and long-distance propagation of individual eddies has garnered extensive attention; however, short-lived MEs (< 7 days) have been widely overlooked. In this study, the basic features of short-lived MEs and their spatial-temporal variations in a tropical eddy-rich region were extracted and analyzed for the first time. Short-lived cyclonic and anticyclonic eddies (CEs/AEs) were found to be widespread in two eddy belts in the tropical region of the western Pacific warm pool (WPWP). The CEs and AEs were formed by the shear instability between large-scale circulations and were distributed on both sides of the North Equatorial Countercurrent, with significant differences in spatial distribution. The variations in sea surface temperature, mixed layer depth, and surface chlorophyll-a concentration in the core of the WPWP were spatially and temporally related to the development of the two eddy belts. This new insight into short-lived MEs in the tropical region contributes to our current understanding of ocean eddies. The potential impacts of short-lived MEs on climate change, global air–sea interactions, and tropical cyclone formation should receive adequate attention and further assessment in future research.

Climate and nutrients regulate biographical patterns and health risks of antibiotic resistance genes in mangrove environment - Huaxian Zhao; Junya Zhang; Xing Chen; Shu Yang; Haifeng Huang; Lianghao Pan; Liangliang Huang; Gonglingxia Jiang; Jinli Tang; Qiangsheng Xu; Ke Dong; Nan Li (Science of The Total Environment, 2023)

Ketamine modulates neural stem cell differentiation by regulating TRPC3 expression through the GSK3β/β-catenin pathway - Ying-Jun She; Junping Pan; Liang-Ming Peng; Li Ma; Xinying Guo; Dong-Xu Lei; Huai-Zhen Wang (NeuroToxicology, 2023)

Ammonia nitrogen recovery from biogas slurry by SCP production using Candida utilis - Hongxia Ding; Jiabao Li; Fang Deng; Siyuan Huang; Pan Zhou; Xiaofeng Liu; Zhidong Li; Dong Li (Journal of Environmental Management, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Characterization of antidiabetic effects of Dendrobium officinale derivatives in a mouse model of type 2 diabetes mellitus - Dong Peng; Wenni Tian; Miaoqing An; Yanlan Chen; Wenshen Zeng; Siyang Zhu; Pan Li; Bing Du (Food Chemistry, 2023)

Crosstalk of oxidative stress, inflammation, apoptosis, and autophagy under reactive oxygen stress involved in difenoconazole-induced kidney damage in carp - Xinyu Wu; Baoshi Xu; Huizhen Chen; Jingchao Qiang; Huimiao Feng; Xueqing Li; Mingyi Chu; Enzhuang Pan; Jingquan Dong (Fish & Shellfish Immunology, 2023)

Distribution of antibiotic resistance genes in the sediments of Erhai Lake, Yunnan-Kweichow Plateau, China: Their linear relations with nonpoint source pollution discharges from 26 tributaries - Xiong Pan; Zeyu Chen; Wenliang Zhai; Lei Dong; Li Lin; Yi Li; Yuyi Yang (Environmental Pollution, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Influence of the upper mixed layer depth on Langmuir turbulence characteristics - Guojing Li; Changming Dong; Jiayi Pan; Adam T. Devlin; Dongxiao Wang (Journal of Oceanology and Limnology, 2023)

Lateral downslope transport and tentative sedimentary organic carbon box model in the southern Yap Trench, western Pacific Ocean - Dong Li; Jun Zhao; Chenggang Liu; Jianming Pan; Ji Hu (Acta Oceanologica Sinica, 2023)

Effects of Nitrogen Reduction and Optimized Fertilization Combined with Straw Return on Greenhouse Gas Emissions and Crop Yields of a Rice–Wheat Rotation System - Hao He; Dandan Li; Feifan Pan; Fengwen Wang; Dong Wu; Shuyun Yang (International Journal of Plant Production, 2022)

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

Lipid metabolism disorders of hybrid grouper (♀Epinephelus fuscointestinestatus × ♂E. lanceolatu) induced by high-lipid diet - Xiangxiang Suo; Xiaobo Yan; Beiping Tan; Simiao Pan; Tao Li; Hao Liu; Weibin Huang; Shuang Zhang; Yuanzhi Yang; Xiaohui Dong (Frontiers in Marine Science, 2022)
This study investigated the effect of lipid levels on growth, body composition, lipid metabolism enzymes activity and related genes expression in hybrid grouper (♀ Epinephelus fuscointestinestatus × ♂ E. lanceolatu ). Three diets with different lipid levels of 6% (low-lipid feed, LF), 11% (medium-lipid feed, MF) and 16% (high-lipid feed, HF) were designed and each diet was fed to triplicate groups of 30 fish each (6.73 ± 0.00g) for eight weeks. The results revealed the following. 1) The maximum weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER) and the lowest feed conversion ratio (FCR) values were found in the HF group. There was no significant difference in the survival rate (SR) among the groups ( P > 0.05). 2) Condition factor (CF), hepatosomatic index (HSI) and visceralsomatic index (VSI) increased with increasing dietary lipid. 3) Crude lipid content in the whole-body and muscle increased significantly as the dietary lipid level increased ( P < 0.05). 4) Principal component analysis of fatty acids showed that sum n-3 polyunsaturated fatty acids (∑n-3PUFA)/sum n-6 polyunsaturated fatty acids (∑n-6PUFA) was significantly higher in the HF group than in the other two groups ( P < 0.05). 5) Biochemical serum indexes showed higher triglycerides (TG), total cholesterol (TC), alkaline phosphatase (AKP) and low-density lipoprotein-cholesterol (LDL-C) levels but lower high-density lipoprotein-cholesterol (HDL-C) level in the HF group. 6) Liver lipid metabolism enzymes activity and biochemical indicators showed that fish fed the MF diet had higher lipoprotein lipase (LPL), hepatic lipase (HL) and triglyceride lipase (ATGL) activity but lower fatty acid synthase (FAS) activity and very-low density lipoprotein-cholesterol (VLDL-C) level. 7) The relative expression levels of lipoprotein lipase ( lpl ), adipocyte-type fatty acid-binding protein ( a-fabp ), liver-type fatty acid-binding protein ( l-fabp ), heart-type fatty acid-binding protein ( h-fabp ) and hormone-sensitive lipase ( hsl ) genes in the fish liver were higher in the MF group with increasing dietary lipid ( P < 0.05), while the fatty acid synthase ( fas ) gene was expressed at lower relative level ( P < 0.05). 8) Histological oil-red sections of the liver showed that fish in the HF group had larger and more hepatic lipid droplets than those fed the other diets. It was concluded that fish fed the HF diet had better growth performance but this diet was not conducive to the progress of lipid metabolism, resulting in lipid accumulation and affecting the quality of the fish. This study provides useful information for the formulation of environmentally friendly and cost-effective diets for hybrid grouper.

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Characteristics, Types, and Prospects of Geological Sweet Sections in Giant Continental Shale Oil Provinces in China - Zhi Yang; Caineng Zou; Songtao Wu; Songqi Pan; Xiaoni Wang; Haitao Liu; Wenqi Jiang; Jiarui Li; Qiyan Li; Xiaobing Niu; Guohui Li; Zhenxing Tang; et al. (Journal of Earth Science, 2022)

Soil-resistant organic carbon improves soil erosion resistance under agroforestry in the Yellow River Flood Plain, of China - Jiachen Pan; Chao Liu; Hongli Li; Qicong Wu; Zhi Dong; Xiaohui Dou (Agroforestry Systems, 2022)

Monitoring periodically national land use changes and analyzing their spatiotemporal patterns in China during 2015–2020 - Wenhui Kuang; Shuwen Zhang; Guoming Du; Changzhen Yan; Shixin Wu; Rendong Li; Dengsheng Lu; Tao Pan; Jing Ning; Changqing Guo; Jinwei Dong; Yuhai Bao; et al. (Journal of Geographical Sciences, 2022)

Effects of vitamin E supplementation of a high-lipid diet on the growth and biochemical parameters of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus) - Weibin Huang; Xiaobo Yan; Hao Liu; Beiping Tan; Xiangxiang Suo; Simiao Pan; Tao Li; Yuanzhi Yang; Xiaohui Dong (Frontiers in Marine Science, 2022)
There is a trend towards using high-lipid diets in aquaculture, which can be optimized by using certain additives. This study investigated the effect of vitamin E (VE) supplementation of a high-lipid diet on the growth, serum and liver biochemical indexes, hepatic histology, and lipid metabolism of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ). Six groups of iso-protein (50.23%) and iso-lipidic high-lipid (15.36%) experimental diets were prepared by adding VE at concentrations of 49.6 (basic diet, controls), 100, 110, 163, 206, and 245 mg/kg. Each treatment consisted of three replicates and 30 fish (10.20 ± 0.02 g) in an 8-week feeding experiment. The results show that 1) compared with controls, growth performance was not affected by VE addition. However, the weight gain rate (WGR) and specific growth rate (SGR) were significantly lower in the high-VE group (245 mg/kg) than in the 163 and 206 mg/kg groups. 2) Compared with controls, VE significantly increased the contents of alpha-tocopherol in the liver and muscle. 3) Adding VE can reduce the fatty livers caused by high-lipid diets and significantly reduce total serum cholesterol, reduce the activity of lipid synthesis enzymes, and significantly increase the activity of lipolytic enzymes in the liver. 4) Compared with controls, appropriate amounts of VE significantly increased the expressions of the liver lipid-metabolism-related genes PPAR-α , PPAR-β , PPAR-γ , H-FABP , A-FABP , and L-FABP . Based on observations of lipid metabolism enzyme activity, histological sections, and lipid-metabolism-related gene expression, we conclude that the addition of 163–206 mg/kg VE to a high-lipid diet can promote lipid metabolism in groupers.

An assessment of the impact threshold and risk of spring-wheat production to climate change in Inner Mongolia, China - Zhiqiang Dong; Zhihua Pan; Xiaoping Xue; Nan Li; Chen Chen; Yanchun Chen (Theoretical and Applied Climatology, 2022)

Experimental study on the effects of particle grading on lime-treated slurry with vacuum preloading - Hong-lei Sun; Zhen-qi Weng; Xue-yu Geng; Meng-fen Shen; Xiao-dong Pan; Li Shi; Yuan-qiang Cai (Marine Georesources & Geotechnology, 2022)

Melatonin inhibits Gram-negative pathogens by targeting citrate synthase - Fang He; Yuan Liu; Pan Li; Xiaoyan Wu; Yaoyao Xia; Dong Zhang; Nengzhang Li; Yuanyi Peng; Guoqiang Zhu; Rüdiger Hardeland; Russel J. Reiter; Wenkai Ren (Science China Life Sciences, 2022)

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

Millifolide A, a dimeric ether of degraded sesquiterpene lactones, inhibited the proliferation of human lung cancer cell line A549 - Pan-Pan Yu; Feng Yu; Wen-Zhe Li; Si-Ming Wang; Chuan Wang; Mei Dong; Zhi-Yu Ni; Yong Li; Hiromasa Kiyota (Natural Product Research, 2022)

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

Comparison of heavy metal speciation, transfer and their key influential factors in vegetable soils contaminated from industrial operation and organic fertilization - Hao Wu; Fengfeng Sui; Huatai Duan; Tianren Si; Hao Li; Jingbo Wang; Xingjie Huang; Lianqing Li; Marios Drosos; Stephen Joseph; Changxun Dong; Genxing Pan (Journal of Soils and Sediments, 2022)

Ecological performance evaluation of urban agriculture in Beijing based on temperature and fractional vegetation cover - Ran Wo; Tianyu Dong; Qidi Pan; Ziyi Liu; Zhaoyang Li; Miaomiao Xie (Urban Ecosystems, 2022)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

Reconstructed annual glacier surface mass balance in the Ányêmaqên Mountains, Yellow River source, based on snow line altitude - Kai-ji Li; Bo Cao; Wei-jin Guan; Bao-tian Pan; Dong-hui Shangguan (Journal of Mountain Science, 2022)

Inhibition of red chlorophyll catabolite reductase improved chlorophyll and carotenoid synthesis in tobacco - Chen Dong; Mei Zhang; Fang Wei; Yushuang Guo; Lili Qin; Pan Wei; Yubo Wang; Lifeng Jin; Weina Song; Tao Sun; Feng Li; Ran Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Biochanin A Sensitizes Glioblastoma to Temozolomide by Inhibiting Autophagy - Qiang Dong; Degui Wang; Lanlan Li; Jie Wang; Qiao Li; Lei Duan; Hang Yin; Xiaoqing Wang; Yang Liu; Guoqiang Yuan; Yawen Pan (Molecular Neurobiology, 2022)

Residential greenness attenuated associations of long-term exposure to air pollution with biomarkers of advanced fibrosis - Jian Hou; Xiaotian Liu; Tantan Zuo; Runqi Tu; Xiaokang Dong; Ruiying Li; Mingming Pan; Ruoling Chen; Shanshan Yin; Kai Hu; Zhenxing Mao; Wenqian Huo; et al. (Environmental Science and Pollution Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Environmental drivers of phytoplankton crops and taxonomic composition in northeastern Antarctic Peninsula adjacent sea area - Yubin Feng; Dong Li; Jun Zhao; Zhengbing Han; Jianming Pan; Gaojing Fan; Haisheng Zhang; Ji Hu; Haifeng Zhang; Jiaqi Wu; Qiuhong Zhu (Acta Oceanologica Sinica, 2022)

Effects of Blade Number on the Propulsion and Vortical Structures of Pre-Swirl Stator Pump-Jet Propulsors - Han Li; Qiaogao Huang; Guang Pan; Xinguo Dong; Fuzheng Li (Journal of Marine Science and Engineering, 2021)
Reducing the noise of the underwater propulsor is gaining more and more attention in the marine industry. The pump-jet propulsor (PJP) is an extraordinary innovation in marine propulsion applications. This paper inspects the effects of blade number on a pre-swirl stator pump-jet propulsor (PJP) quantitatively and qualitatively. The numerical calculations are conducted by IDDES and ELES, where the ELES is only adopted to capture the vortical structures after refining the mesh. The numerical results show good agreement with the experiment. Detailed discussions of the propulsion, the features of thrust fluctuation in time and frequency domains, and the flow field are involved. Based on the ELES results, the vortices in the PJP flow field and the interactions between the vortices of the stator, rotor, and duct are presented. Results suggest that, though changing the blade number under a constant solidity does not affect the propulsion, it has considerable effects on the thrust fluctuation of PJP. The wakes of the stator and rotor are also notably changed. Increasing the stator blade numbers has significantly weakened the high-intensity vortices in the stator wake and, hence, the interaction with the rotor wake vortices. The hub vortices highly depend upon the wake vortices of the rotor. The hub vortices are considerably broken by upstream wake vortices when the load per rotor blade is high. In summary, the blade number is also vital for the further PJP design, particularly when the main concerns are exciting force and noise performance.

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Two new alkaloids from the sepals of Solanum melongena L - Dong-Ying Zhao; Yan Liu; Xin Yin; Xiao-Mao Li; Juan Pan; Wei Guan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2021)

Neuroprotective Effect of Fractalkine on Radiation-induced Brain Injury Through Promoting the M2 Polarization of Microglia - Jiaojiao Wang; Huijiao Pan; Zhenyu Lin; Chunjin Xiong; Chunhua Wei; Huanhuan Li; Fan Tong; Xiaorong Dong (Molecular Neurobiology, 2021)
Radiation-induced brain injury (RIBI) is a serious complication in cancer patients receiving brain radiotherapy, and accumulating evidence suggests that microglial activation plays an important role in its pathogenesis. Fractalkine (FKN) is a crucial mediator responsible for the biological activity of microglia. In this study, the effect of FKN on activated microglial after irradiation and RIBI was explored and the underlying mechanisms were investigated. Our study demonstrated treatment with exogenous FKN diminished radiation-induced production of pro-inflammatory factors, such as IL1-β and TNFα, promoted transformation of microglial M1 phenotype to M2 phenotype after irradiation, and partially recovered the spatial memory of irradiated mice. Furthermore, upregulation of FKN/CX3CR1 via FKN lentivirus promoted radiation-induced microglial M2 transformation in the hippocampus and diminished the spatial memory injury of irradiated mice. Furthermore, while inhibiting the expression of CX3CR1, which exclusively expressed on microglia in the brain, the regulatory effect of FKN on microglia and cognitive ability of mice disappeared after radiation. In conclusion, the FKN could attenuate RIBI through the microglia polarization toward M2 phenotype by binding to CX3CR1 on microglia. Our study unveiled an important role of FKN/CX3CR1 in RIBI, indicating that promotion of FKN/CX3CR1 axis could be a promising strategy for the treatment of RIBI.

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

LncRNA SNHG7 sponges miR-449a to promote pituitary adenomas progression - Xiongfei Yue; Ce Dong; Zhanying Ye; Lin Zhu; Xiaoyang Zhang; Xiaoyan Wang; Feng Mo; Zheng Li; Baogen Pan (Metabolic Brain Disease, 2021)

Three-dimensional numerical modeling of water distribution tunnels in karst area - Xiao-dong Pan; Yu-chao Fang; Yong Lai; Hong-lei Sun; Yuan-qiang Cai; Li Shi; Xue-yu Geng (Arabian Journal of Geosciences, 2020)

Glycerol transporter 1 (Gt1) and zinc-regulated transporter 1 (Zrt1) function in different modes for zinc homeostasis in Komagataella phaffii (Pichia pastoris) - Yankun Yang; Yingyue Pan; Guoqiang Liu; Guibin Dong; Chunjun Zhan; Mattheos A. G. Koffas; Xiuxia Liu; Ye Li; Chunli Liu; Zhonghu Bai (Biotechnology Letters, 2020)

Transcriptomic Analysis of Liver Tissue in Fat Greenling (Hexagrammos otakii) Exposed to Elevated Ambient Ammonia - Li Li; Fengxiang Gao; Yuxia Jian; Xue Wang; Xiaolong Wang; Lei Pan; Wen Guo; Dong Liu; Fawen Hu (Frontiers in Marine Science, 2020)

The role of endogenous and exogenous hydrogen in the microbiology of biogas production systems - Xianpu Zhu; Pan Zhou; Yichao Chen; Xiaofeng Liu; Dong Li (World Journal of Microbiology and Biotechnology, 2020)

Diverse Asgard archaea including the novel phylum Gerdarchaeota participate in organic matter degradation - Mingwei Cai; Yang Liu; Xiuran Yin; Zhichao Zhou; Michael W. Friedrich; Tim Richter-Heitmann; Rolf Nimzyk; Ajinkya Kulkarni; Xiaowen Wang; Wenjin Li; Jie Pan; Yuchun Yang; et al. (Science China Life Sciences, 2020)

Effects of Bacillus cereus PAS38 on Immune-Related Differentially Expressed Genes of Spleen in Broilers - Xiaoxiao Gu; Jiao Zhang; Jiajun Li; Zhenhua Wang; Jie Feng; Jianzhen Li; Kangcheng Pan; Xueqin Ni; Dong Zeng; Bo Jing; Dongmei Zhang (Probiotics and Antimicrobial Proteins, 2020)

Lignite-Activated Carbon Grafted PAA Combined with Conventional Drinking Water Treatment Processes for the Emergency Removal of Trace Pb(II) Pollution - Lihua Dong; Shujie Pan; Zhansheng Wang; Li’an Hou; G. Zhou; Guanyi Chen (Water, Air, & Soil Pollution, 2020)

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

MicroRNA-498 inhibits the proliferation, migration and invasion of gastric cancer through targeting BMI-1 and suppressing AKT pathway - Dong You; Dawei Wang; Peiji Liu; Yuning Chu; Xueying Zhang; Xueli Ding; Xiaoyu Li; Tao Mao; Xue Jing; Zibin Tian; Yinghua Pan (Human Cell, 2020)

The transcription factor PrtT and its target protease profiles in Aspergillus niger are negatively regulated by carbon sources - Lianggang Huang; Liangbo Dong; Bin Wang; Li Pan (Biotechnology Letters, 2020)

Effects of subterranean termite nest architectures on earth embankment seepage and stability - Ying Li; Zhi-Yong Dong; Dong-Zi Pan; Cun-Hong Pan (Paddy and Water Environment, 2020)

The Arabidopsis UDP-glycosyltransferase75B1, conjugates abscisic acid and affects plant response to abiotic stresses - Ting-Ting Chen; Fang-Fei Liu; Dong-Wang Xiao; Xiao-Yi Jiang; Pan Li; Shu-Man Zhao; Bing-kai Hou; Yan-jie Li (Plant Molecular Biology, 2020)

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

The complete chloroplast genome of Loropetalum subcordatum, a national key protected species in China - Yunyan Zhang; Huixia Cai; Jiaxian Dong; Wei Gong; Pan Li; Zhongsheng Wang (Conservation Genetics Resources, 2019)

Distribution characteristics and pollution risk evaluation of the nitrogen and phosphorus species in the sediments of Lake Erhai, Southwest China - Xiong Pan; Li Lin; Zhuo Huang; Min Liu; Lei Dong; Jin Chen; John Crittenden (Environmental Science and Pollution Research, 2019)

Gadolinium chloride promotes proliferation of HEK293 human embryonic kidney cells by activating EGFR/PI3K/Akt and MAPK pathways - Xin Pan; Jinxia Li; Xia He; Jianjun Deng; Faqin Dong; Kui Wang; Siwang Yu (BioMetals, 2019)

Archaeal community structure in sediments from a seamount in the Mariana Volcanic Arc - Wenyan Zhang; Jia Liu; Yi Dong; Xuegang Li; Cong Xu; Tian Xiao; Hongmiao Pan; Long-Fei Wu (Journal of Oceanology and Limnology, 2019)

Influence of stochastic modeling for inter-system biases on multi-GNSS undifferenced and uncombined precise point positioning - Feng Zhou; Danan Dong; Pan Li; Xin Li; Harald Schuh (GPS Solutions, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

3D-RVSP experimental study above a carbonate outcrop for coal resource exploration - Mingshun Hu; Dongming Pan; Juanjuan Li; Hui Zhang; Shouhua Dong; Shenen Chen; Yongzhong Xu (Acta Geophysica, 2019)

Identification and Functional Characterization of the DcF3’H Promoter from Dracaena cambodiana - Jiahong Zhu; Pan Chen; Dong Guo; Huiliang Li; Ying Wang; Haofu Dai; Wenli Mei; Shiqing Peng (Tropical Plant Biology, 2018)

The complete chloroplast genome of Caryopteris mongholica and phylogenetic implications in Lamiaceae - Luxian Liu; Chuying Zhang; Yuewen Wang; Meifang Dong; Fude Shang; Pan Li (Conservation Genetics Resources, 2018)

Mechanical behavior and micro-structure of cement kiln dust-stabilized expensive soil - Su Li Cui; Jia Ding Wang; Xiao Dong Wang; Yan Feng Du; Xue Pan Wang (Arabian Journal of Geosciences, 2018)

Enhancing Stability of Exenatide-Containing Pressurized Metered-Dose Inhaler Via Reverse Microemulsion System - Xing Li; Ying Huang; Zhengwei Huang; Xiangyu Ma; Ni Dong; Wanxin Chen; Xin Pan; Chuanbin Wu (AAPS PharmSciTech, 2018)

Emerging role of semaphorin-3A in autoimmune diseases - Li-Na Liu; Xiao-Mei Li; Dong-Qing Ye; Hai-Feng Pan (Inflammopharmacology, 2018)

Over-expression of the Pseudomonas syringae harpin-encoding gene hrpZm confers enhanced tolerance to Phytophthora root and stem rot in transgenic soybean - Qian Du; Xiangdong Yang; Jinhua Zhang; Xiaofang Zhong; Kyung Seok Kim; Jing Yang; Guojie Xing; Xiaoyu Li; Zhaoyuan Jiang; Qiyun Li; Yingshan Dong; Hongyu Pan (Transgenic Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Simultaneous estimation of GLONASS pseudorange inter-frequency biases in precise point positioning using undifferenced and uncombined observations - Feng Zhou; Danan Dong; Maorong Ge; Pan Li; Jens Wickert; Harald Schuh (GPS Solutions, 2018)

Kinesin KIF4A is associated with chemotherapeutic drug resistance by regulating intracellular trafficking of lung resistance-related protein - Li-na Pan; Yuan Zhang; Chang-jun Zhu; Zhi-xiong Dong (Journal of Zhejiang University-SCIENCE B, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

Tripchlorolide Attenuates β-amyloid Generation via Suppressing PPARγ-Regulated BACE1 Activity in N2a/APP695 Cells - Nan Lin; Li-min Chen; Xiao-dong Pan; Yuan-gui Zhu; Jing Zhang; Yan-qing Shi; Xiao-chun Chen (Molecular Neurobiology, 2016)

Water quality assessment of benthic diatom communities for water quality in the subalpine karstic lakes of Jiuzhaigou, a world heritage site in China - Li-li Ouyang; Yang-dong Pan; Cheng-min Huang; Ya Tang; Jie Du; Wei-yang Xiao (Journal of Mountain Science, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Analysis the role of arabidopsis CKRC6/ASA1 in auxin and cytokinin biosynthesis - Dong-Wei Di; Lei Wu; Pan Luo; Li Zhang; Tian-Zi Zhang; Xue Sun; Shao-Dong Wei; Chen-Wei An; Guang-Qin Guo (Journal of Plant Biology, 2016)

Risk assessment of maize drought disaster in southwest China using the Environmental Policy Integrated Climate model - Hui-cong Jia; Dong-hua Pan; Jing Li; Wan-chang Zhang; Rasul Ghulam (Journal of Mountain Science, 2016)

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis - Mei-Yun Huang; Hao Pan; Yi-Dan Liang; Hong-Xia Wei; Li-Hui Xu; Qing-Bing Zha; Xian-Hui He; Dong-Yun Ouyang (Apoptosis, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

PEDF and 34-mer inhibit angiogenesis in the heart by inducing tip cells apoptosis via up-regulating PPAR-γ to increase surface FasL - Hao Zhang; Tengteng Wei; Xia Jiang; Zhimin Li; Huazhu Cui; Jiajun Pan; Wei Zhuang; Teng Sun; Zhiwei Liu; Zhongming Zhang; Hongyan Dong (Apoptosis, 2016)

Deghosting towed streamer data in τ/p domain based on rough sea surface reflectivity - Xing-Yan Zhang; Dong-Ming Pan; Wen-Ying Shi; Zhong-Yu Fang; Zhi-Wei Dan; Li-Xia Zhang (Applied Geophysics, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Satellite remote sensing of ultraviolet irradiance on the ocean surface - Teng Li; Delu Pan; Yan Bai; Gang Li; Xianqiang He; Chen-Tung Arthur Chen; Kunshan Gao; Dong Liu; Hui Lei (Acta Oceanologica Sinica, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

The decreased frequency of SIGIRR-positive CD4+ T cells in peripheral blood of patients with SLE and its correlation with disease activity - Dao-Yang Wang; Chao Su; Gui-Mei Chen; Hai-Feng Pan; Feng-Mei Wang; Gui-Ling Liu; Li Hao; De-Guang Wang; Dong-Qing Ye (Molecular Biology Reports, 2015)

Occurrence, removal, and fate of progestogens, androgens, estrogens, and phenols in six sewage treatment plants around Dianchi Lake in China - Bin Huang; Xiaoman Li; Wenwen Sun; Dong Ren; Xiao Li; Xiaonan Li; Ying Liu; Qiang Li; Xuejun Pan (Environmental Science and Pollution Research, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Platelet-derived growth factor mediates interleukin-13-induced collagen I production in mouse airway fibroblasts - Jiamei Lu; Yanting Zhu; Wei Feng; Yilin Pan; Shaojun Li; Dong Han; Lu Liu; Xinming Xie; Guizuo Wang; Manxiang Li (Journal of Biosciences, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Genome-wide identification and phylogenetic analysis of Family-1 UDP glycosyltransferases in maize (Zea mays) - Yanjie Li; Pan Li; Yong Wang; Ruirui Dong; Huimin Yu; Bingkai Hou (Planta, 2014)

Engrailed-2 is down-regulated but also ectopically expressed in clear cell renal cell carcinoma - Cai-yong Lai; Bin Pan; Yun Luo; Wei-bo Liang; Jie Chen; Dong-ming Ye; Ji-Nan Guo; Li Li; Ze-xuan Su (Molecular Biology Reports, 2014)

Influence of the composition and removal characteristics of organic matter on heavy metal distribution in compost leachates - Xiao-Song He; Bei-Dou Xi; Dan Li; Xu-Jing Guo; Dong-Yu Cui; Hong-Wei Pan; Yan Ma (Environmental Science and Pollution Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Improved yield and Zn accumulation for rice grain by Zn fertilization and optimized water management - Yu-yan Wang; Yan-yan Wei; Lan-xue Dong; Ling-li Lu; Ying Feng; Jie Zhang; Feng-shan Pan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Functional Analysis of a Novel Chrysanthemum WRKY Transcription Factor Gene Involved in Salt Tolerance - Qing-Lin Liu; Ke-Dong Xu; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Plant Molecular Biology Reporter, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Overexpression of a novel chrysanthemum Cys2/His2-type zinc finger protein gene DgZFP3 confers drought tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Ming Zhong; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Biotechnology Letters, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Cloning, promoter analysis and expression of the tumor necrosis factor receptor-associated factor 6 (TRAF6) in Japanese scallop (Mizuhopecten yessoensis) - Chong-bo He; Yang Wang; Wei-dong Liu; Xiang-gang Gao; Pan-hai Chen; Yun-feng Li; Xiang-bo Bao (Molecular Biology Reports, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Erratum to: Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Adaptation of spherical multicellular magnetotactic prokaryotes to the geochemically variable habitat of an intertidal zone - Ke Zhou; Wen‐Yan Zhang; Hong‐Miao Pan; Jin‐Hua Li; Hai‐Dong Yue; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2013)
Summary A combination of microscopic, molecular and biogeochemical methods was used to study the structure, phylogenetics and vertical distribution of spherical multicellular magnetotactic prokaryotes ( MMPs ) of intertidal sediments in the Y ellow S ea. These MMPs were 5.5 μm in diameter and composed of approximately 15–30 cells. They synthesized bullet‐shaped magnetites in chains or clusters. Phylogenetic analysis of 16 S rRNA gene sequences suggested that these MMPs represent a novel species affiliated to the D eltaproteobacteria. To study their vertical distribution and the relationship to geochemical parameters, sediment cores were collected after the redox potential was measured in situ . The sediments were composed of yellow, grey and black layers from the surface to depth. The spherical MMPs were concentrated near the grey‐black layer transition at a depth of 8–12 cm, while coccoid‐shaped magnetotactic bacteria near the yellow‐grey layer transition at a depth of 3–5 cm. The intertidal MMPs showed a deeper distribution at more reduced environments than coccoid‐shaped magnetotactic bacteria, and MMPs in lagoon sediments. Additionally the MMPs were concentrated significantly in layers with high proportion of fine sand and total organic carbon, rich in leachable iron but poor in nitrate. These results show an adaptation of spherical MMPs to the peculiar intertidal sediment habitat.

Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Association of RANTES and MBL gene polymorphisms with systemic lupus erythematosus: a meta-analysis - Wang-Dong Xu; Hui Peng; Mo Zhou; Min Zhang; Bao-Zhu Li; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Isolation of yellow catfish β-actin promoter and generation of transgenic yellow catfish expressing enhanced yellow fluorescent protein - Jiachun Ge; Zhangji Dong; Jingyun Li; Zhiqiang Xu; Wei Song; Jie Bao; Dong Liang; Junbo Li; Kui Li; Wenshuang Jia; Muzi Zhao; Yongxiang Cai; et al. (Transgenic Research, 2012)

Cells scaffold complex for Intervertebral disc Anulus Fibrosus tissue engineering: in vitro culture and product analysis - Yong Pan; Tongwei Chu; Shiwu Dong; Yong Hao; Xianjun Ren; Jian Wang; Weidong Wang; Changqing Li; Zhengfeng Zhang; Yue Zhou (Molecular Biology Reports, 2012)

High incidence of plasmids in marine Vibrio species isolated from Mai Po Nature Reserve of Hong Kong - Ruifu Zhang; Li Pan; Zhenye Zhao; Ji-Dong Gu (Ecotoxicology, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

SK channels modulate the excitability and firing precision of projection neurons in the robust nucleus of the arcopallium in adult male zebra finches - Guo-Qiang Hou; Xuan Pan; Cong-Shu Liao; Song-Hua Wang; Dong-Feng Li (Neuroscience Bulletin, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

Chemoresistance to Temozolomide in Human Glioma Cell Line U251 is Associated with Increased Activity of O 6-methylguanine-DNA Methyltransferase and Can be Overcome by Metronomic Temozolomide Regimen - Qiang Pan; Xue-jun Yang; Hua-min Wang; Xue-tao Dong; Wei Wang; Yu LI; Jing-min LI (Cell Biochemistry and Biophysics, 2012)

Meta-analysis of TYK2 gene polymorphisms association with susceptibility to autoimmune and inflammatory diseases - Jin-Hui Tao; Yan-Feng Zou; Xiao-Liang Feng; Jing Li; Fang Wang; Fan-Ming Pan; Dong-Qing Ye (Molecular Biology Reports, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Overexpression of a novel chrysanthemum NAC transcription factor gene enhances salt tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Liang-Jun Zhao; Yuan-Zhi Pan; Bei-Bei Jiang; Hai-Qing Zhang; Guang-Li Liu (Biotechnology Letters, 2011)

Cloning and Expression of One Chloroplastic Ascorbate Peroxidase Gene from Nelumbo nucifera - Chen Dong; Xingfei Zheng; Guolin Li; Cheng Pan; Mingquan Zhou; Zhongli Hu (Biochemical Genetics, 2011)

Interleukin-21 as a potential therapeutic target for systemic lupus erythematosus - Jing Li; Hai-Feng Pan; Han Cen; Jing Tian; Yan Ma; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)

Verapamil exerts biphasic modulation on phenobarbital transport across the blood–brain barrier: evidence from an in vivo and in vitro study - Dan Yao; Zhi-Hong Yang; Li Liu; Jia Li; Yun-Li Yu; Lu-Lu Zhang; Xian Pan; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

TWEAK as a target for therapy in systemic lupus erythematosus - Rui-Xue Leng; Hai-Feng Pan; Wei-Zi Qin; Chao Wang; Li-Li Chen; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

An ordered EST catalogue and gene expression profiles of cassava (Manihot esculenta) at key growth stages - You-Zhi Li; Ying-Hua Pan; Chang-Bin Sun; Hai-Tao Dong; Xing-Lu Luo; Zhi-Qiang Wang; Ji-Liang Tang; Baoshan Chen (Plant Molecular Biology, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Numerical simulation scattered imaging in deep mines - Ming-Shun Hu; Dong-Ming Pan; Juan-Juan Li (Applied Geophysics, 2010)

Post-conditioning protects cardiomyocytes from apoptosis via PKCε-interacting with calcium-sensing receptors to inhibit endo(sarco)plasmic reticulum–mitochondria crosstalk - Shiyun Dong; Zongyan Teng; Fang-hao Lu; Ya-jun Zhao; Hulun Li; Huan Ren; He Chen; Zhen-wei Pan; Yan-jie Lv; Bao-feng Yang; Ye Tian; Chang-qing Xu; et al. (Molecular and Cellular Biochemistry, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Anti-α-actinin antibodies in relation to new-onset systemic lupus erythematosus and lupus nephritis - Wen-Hui Zhang; Hai-Feng Pan; Xue-Fei Zhao; Dong-Qing Ye; Xiang-Pei Li; Jian-Hua Xu (Molecular Biology Reports, 2010)

High Mobility Group Box 1: a potential therapeutic target for systemic lupus erythematosus - Hai-Feng Pan; Guo-Cui Wu; Wei-Ping Li; Xiang-Pei Li; Dong-Qing Ye (Molecular Biology Reports, 2010)

TIM-3 as a new therapeutic target in systemic lupus erythematosus - Hai-Feng Pan; Ning Zhang; Wen-Xian Li; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Association study of a single nucleotide polymorphism in the exon 2 region of toll-like receptor 9 (TLR9) gene with susceptibility to systemic lupus erythematosus among Chinese - Chang-Juan Xu; Wen-Hui Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Dong-Qing Ye (Molecular Biology Reports, 2009)

Fas expression on peripheral blood lymphocytes in systemic lupus erythematosus: relation to the organ damage and lymphocytes apoptosis - Lian-Hong Li; Wen-Xian Li; Ou Wu; Guo-Qing Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Hong Dai; Dong-Qing Ye (Molecular Biology Reports, 2009)

Meta analysis on the association between FcγRIIa-R/H131 polymorphisms and systemic lupus erythematosus - Hui Yuan; Hai-Feng Pan; Lian-Hong Li; Jin-Bao Feng; Wen-Xian Li; Xiang-Pei Li; Dong-Qing Ye (Molecular Biology Reports, 2009)

Resistance gene analog polymorphisms (RGAPs) in wild emmer wheat (Triticum dicoccoides) and their ecological associations - Pan Dong; Yu-Ming Wei; Guo-Yue Chen; Wei Li; Eviatar Nevo; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)